Longer-term neurological and endocrine/metabolic conditions in the deepwater horizon oil spill coast guard cohort study: A principal component analysis - Hristina Denic-Roberts; Jordan McAdam; Lawrence S. Engel; Jeanine M. Buchanich; Rachel G. Miller; Evelyn O. Talbott; Dana L. Thomas; Glen A. Cook; Blake Hansen; Jill E. Emerick; Tina Costacou; Jennifer A. Rusiecki (International Archives of Occupational and Environmental Health, 2026)
Purpose Deepwater Horizon oil spill (DWHOS) responders potentially experienced multiple stressors. We examined associations between DWHOS deployment-related stressor patterns and neurological and endocrine/metabolic conditions among U.S. Coast Guard active duty responders who completed post-deployment surveys (n = 3102). Methods Deployment-related stressor patterns were identified using principal component analysis of self-reported stressors. Neurological and endocrine/metabolic outcomes were classified from military health encounter records. Associations between principal components (PCs) and incident outcomes (2010–2015) were estimated through Cox proportional hazards regression. Results A five-component solution explained 79.2% of the variance. PC1 (high physical/moderate chemical stressor pattern) was associated with migraine [adjusted hazard ratio (aHR): 1.25, 95% confidence interval (CI): 1.01–1.56]. PC2 (high crude oil/dispersant stressor pattern) was associated with several migraine/headache conditions including migraine with aura (1.54, 1.14–2.07), mononeuritis of upper limb and mononeuritis multiplex (1.36, 1.11–1.68), disorders of lipid metabolism (1.11, 1.01–1.23 ) and its subcategory other and unspecified hyperlipidemia (1.11, 1.01–1.24), and dysmetabolic syndrome X (1.74, 1.19–2.54). PC3 (high fatigue/moderate chemical inhalation stressor pattern) was associated with several migraine/headache conditions (aHR range: 1.18–1.60), disorders of lipid metabolism (1.11, 1.00–1.23) including other and unspecified hyperlipidemia (1.13, 1.01–1.26) , and overweight and obesity (1.13, 1.00–1.27). PC4 (high anxiety/modest fatigue stressor pattern) was associated with abnormality of gait (1.34, 1.03–1.73). PC5 (high back pain) was associated with mononeuritis of lower limb, several balance and gait-related conditions , thyroid disorders, and obesity (aHRs range: 1.16–1.67). Conclusion Oil spill response stressor patterns were associated with increased risks of multiple longer-term neurological and endocrine/metabolic conditions, with associations varying by PC.

Formal Mentorship and Leadership Training Contributes to the Development and Expertise of Graduate Students as Teachers, Scientists, and Engineers - Parker J. Esswein; Clare B. Cook; Lailah Ligons; Kiarra Richardson; Marc A. Sommer; Cameron M. Kim (Biomedical Engineering Education, 2026)

A climate services organization supporting coastal resilience: lessons from the Stone Living Lab - K. A. Dafforn; M. Borrelli; K. Bosma; J. E. K. Byrnes; L. Castro-Diaz; R. F. Chen; J. Christo; D. Cook; F. Peri; R. Shoer; M. Albert; K. Bradley; et al. (Climatic Change, 2026)
There is a growing recognition that effective climate adaptation requires organizations that can translate science into policy-relevant, place-based implementation. The Stone Living Lab (SLL) was established as a climate services organization to help bridge the gap between climate adaptation research and real-world application. In this paper, we present the Lab as a model for how universities and NGOs can partner with government agencies, Indigenous groups, and local communities to strengthen coastal resilience, highlighting the structures, guiding principles and lessons learned over the last five years. Four guiding principles shape and distinguish the Lab’s approach, extending beyond the traditional focus on science and engineering research to also include climate preparedness, education and outreach and policy engagement. These principles continue to evolve in response to experience, particularly in navigating complex partnerships and engaging with stakeholder networks, which require sustained coordination, clear communication, and intentional alignment of roles, expectations, and timelines. Other lessons highlight the importance of visible, place-based solutions, knowledge sharing and maintaining a clear mission focus while balancing short-term outcomes with long-term resilience goals. Our aim here is to provide practical insights for researchers, practitioners and managers seeking to design or strengthen similar climate services organizations.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Ocean warming (OW) and freshening influence metabolism and cellular damage in Loxechinus albus at the extremes of their Patagonian distribution - Paola A. Villanueva; Jorge M. Navarro; Sebastián Cook; Danae Paredes; Joseline Büchner-Miranda; Eduardo Ramírez-Kuschel; Ignacio Echeverría; Víctor M. Cubillos; Carlos Lara; Marcela Astorga (Marine Pollution Bulletin, 2026)

A systems modelling approach to predict biological responses to extreme heat - Daniel W.A. Noble; Margaret M. Mayfield; Ary A. Hoffmann; Zhong-Hua Chen; Steven J. Lade; Xuemei Bai; Danielle A. Way; Belinda E. Medlyn; Owen K. Atkin; Adrienne B. Nicotra; James M. Cook; Brajesh K. Singh; et al. (Trends in Ecology & Evolution, 2026)

American oak imports to Britain and Ireland in the 18th and early 19th centuries; The dendrochronological evidence - A. Crone; A. Arnold; R. Bale; M. Bridge; D. Brown; E. Cook; C. Griggs; R. Howard; D. Miles; C. Mills; N. Nayling; C. Tyers; et al. (Dendrochronologia, 2026)

Simultaneous detection of multiple viral pathogens in vacuumed dust from different building types - Austin Shamblin; Calissa Carlisle; Nicholas Nastasi; Genny M. Cook; Anthony C. Fries; Richard T. Agans; Seth Faith; Michael G. Sovic; Vanessa A. Varaljay; Karen C. Dannemiller (Building and Environment, 2026)

Corrigendum to ‘A national-scale preliminary overview study of poly- and perfluoroalkyl substances (PFAS) occurrence in aquatic environments of England, UK’ [Chemosphere 394 (2026) 144804] - R.J. Patel; D.C. Gooddy; B. Marchant; D.J. Lapworth; A. James; M. Cook; K. Darby; T. Besien (Chemosphere, 2026)

Morphological and heat-tolerance traits are associated with progression and impact of, but not vulnerability to, tree decline - Sabina M. Aitken; Pieter A. Arnold; Matthew T. Brookhouse; Alicia M. Cook; Lisa M. Danzey; Rosalie J. Harris; Andy Leigh; Adrienne B. Nicotra (Forest Ecology and Management, 2026)

Associations between air pollution and markers of neuroinflammation, synaptic dysfunction and core Alzheimer’s disease pathology vary by APOE genotype - Kana Kimura; Ira Driscoll; Noah Cook; Sonia Shahzad; Tobey J. Betthauser; Sterling C. Johnson; Sanjay Asthana; Catherine L. Gallagher; Bruce P. Hermann; Mark A. Sager; Kaj Blennow; Henrik Zetterberg; et al. (Neurotoxicity Research, 2026)
To determine whether long-term residential air pollution [AP; ozone (O₃) and fine particulate matter (PM₂.₅)] is associated with (1) incident mild cognitive impairment (MCI) or Alzheimer’s disease (AD), (2) biomarkers of core and AD-relevant pathology, and (3) whether these relationships are moderated by APOE4+/- (carrier/non-carrier of one or both ε4 alleles) status or mediated by neuroinflammation. Sample included 795 participants (Mage 68.7 ± 7.9; 68% female) from the Wisconsin Alzheimer’s Disease Research Center and Wisconsin Registry for Alzheimer’s Prevention parent studies, both enriched for AD risk at enrollment based on parental AD history. Residential zip code and 2009–2021 EPA-based annual AP reports were used to estimate individual exposure. Cox proportional hazards models assessed MCI/AD risk. Linear regressions examined the relationships between AP exposure and biomarkers of core and AD-relevant pathology, with and without APOE4 + stratification. Causal mediation analysis examined whether markers of inflammation mediated the AP-AD pathology relationships. Neither O₃ nor PM₂.₅ exposure predicted MCI/AD incidence nor core AD pathology (Ps > 0.05). Higher PM₂.₅ was associated with higher CSF GFAP levels ( P = 0.003). APOE4 + with higher levels of PM₂.₅ exposure had higher CSF levels of tTau ( P = 0.01), pTau₁₈₁ ( P = 0.01) and neurogranin ( P = 0.02). These relationships were not mediated by neuroinflammation (Ps > 0.05). In this AD-risk enriched cohort, AP was not associated with MCI/AD incidence. However, higher PM₂.₅ exposure was associated with astrocytic activation, and in APOE4+, AD pathology, neurodegeneration, and synaptic dysfunction. Our findings suggest AP as an environmental risk factor contributing to AD-relevant pathology, particularly among genetically at-risk individuals.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

A Dominant Founder Lineage Has Possible Fitness Costs for the Endangered Mexican Grey Wolf - Yeraldi Loera; Manisha Khakoo; Emily Krueckeberg; Ingrid G. Nilsson; Zehao Wu; Maggie Dwire; Jennifer Adams; Lisette Waits; John K. Oakleaf; Mariel L. Campbell; Jonathan L. Dunnum; Joseph A. Cook; et al. (Molecular Ecology, 2026)
The Mexican grey wolf ( Canis lupus baileyi ) is an endangered and genetically distinct subspecies of grey wolf adapted to the warm climates of the southwestern United States and Mexico. Following centuries of eradication efforts, Mexican grey wolves were protected under the Endangered Species Act in 1976, prompting an international ex situ breeding program to preserve their genetic legacy. Seven remnant wolves founded the three distinct lineages of this program: McBride, Ghost Ranch, and Aragón. However, concerns of rising inbreeding levels motivated the implementation of inter‐lineage pairings to decelerate genetic erosion. To evaluate the genetic health of the ex situ managed population, we analysed genome‐wide variation across several generations of breeding wolves and their descendants ( n = 179). Despite ongoing conservation interventions, we found a sharp decline in effective population size over the past 50 generations. However, estimates of inbreeding diminished over time following the inter‐lineage pairings, reflecting efficient pedigree management or potential fitness costs of inbreeding depression, as higher levels of inbreeding and autozygosity were associated with reduced lifespan and reproductive performance. Increasing contributions of Ghost Ranch and Aragón ancestry also aided in reducing levels of inbreeding observed in the more genetically distinct McBride lineage. These findings highlight the challenges of maintaining genetic diversity in bottlenecked populations, reveal fine‐scale patterns of inbreeding within the pedigree and underscore the urgent need to preserve genetic contributions from all founder lineages. Genomic insights from this study can guide breeding strategies to reduce kinship, balance ancestry and mitigate inbreeding depression, safeguarding the evolutionary legacy and the long‐term persistence of the Mexican grey wolf.

A national-scale preliminary overview study of poly- and perfluoroalkyl substances (PFAS) occurrence in aquatic environments of England, UK - R.J. Patel; D.C. Gooddy; B. Marchant; D.J. Lapworth; A. James; M. Cook; K. Darby; T. Besien (Chemosphere, 2026)

Collaborative evaluation of in silico predictions for high throughput toxicokinetics - John F. Wambaugh; Nisha S. Sipes; Gilberto Padilla Mercado; Jon A. Arnot; Linda Bertato; Trevor N. Brown; Nicola Chirico; Christopher Cook; Daniel E. Dawson; Sarah E. Davidson-Fritz; Stephen S. Ferguson; Michael-Rock Goldsmith; et al. (Toxicology in Vitro, 2026)

Exploring Marine Mammal Cognition as a Conservation Tool - Gordon B. Bauer; Peter F. Cook; Heidi E. Harley; Jason Bruck; Mel Cosentino; Charles J. Deutsch; Nicola Erdsack; Wendi Fellner; Tabitha Gunnars; Heather Manitzas Hill; Sonia V. Kumar; Malin K. Lilley; et al. (Marine Mammal Science, 2026)
Cognition is an animal's real‐time adaptation system for responding to change. Rapid environmental change, often anthropogenic, is expanding the range and severity of challenges confronting wild animals. Effective conservation requires a multifaceted approach that includes animals' capacities. Large‐brained, long‐lived animals such as marine mammals often have extensive capability to adaptively modify their behavior due to their cognition, which comprises the mechanisms of information acquisition, processing, and flexible action. Consequently, current behavior need not be a final predictor of future behavior for these animals. This flexibility provides an underutilized and under examined point of leverage for humans interested in improving life outcomes for wild animals. In this team‐written, interdisciplinary paper, we argue that application of cognitive approaches may facilitate many conservation efforts directed toward marine mammals. Starting with a workshop on this topic at the 24th Biennial Conference on the Biology of Marine Mammals, scientists representing a wide range of disciplinary expertise addressed eight different conservation concerns for six marine mammal species and provided potential cognitive explanations of and interventions aimed at related behavior. Our treatment highlights the value of integrated laboratory and field research, and the importance of tight lines of communication between scientists and conservation managers.

Metabolic and survival responses of the carnivorous snail Acanthina monodon to extreme marine heatwaves - Paola A. Villanueva; Joseline A. Büchner-Miranda; Jorge M. Navarro; Sebastián Cook; Octavio Mercado-Peña; Paula Amador-Véliz; Gonzalo Donoso; Elisabeth Teca Oliva; Oscar R. Chaparro (Regional Studies in Marine Science, 2025)

Corrigendum to Toward a near-lossless image compression strategy for the NASA/USGS Landsat Next mission Remote Sensing of Environment Volume 329, 1 November 2025, 114929 - Rehman S. Eon; Craig De Groot; Jeffrey A. Pedelty; Aaron Gerace; Matthew Montanaro; Richard K. Covington; Amy S. DeLisa; Wen-Ting Hsieh; Joy M. Henegar-leon; Douglas J. Daniels; Christopher Engebretson; Christopher J. Crawford; et al. (Remote Sensing of Environment, 2025)

A decision support tool for rubble stabilization on coral reefs - Shu Kiu Leung; Tania M. Kenyon; Laurie J. Raymundo; Helen E. Fox; Nathan Cook; Kailash Cook; Alasdair J. Edwards; Eric E. Fisher; Arnaud J.T. Brival; Freda E. Nicholson; Robin W.L. Philippo; Andrew C.F. Taylor; et al. (Journal of Environmental Management, 2025)

Examining Explicit Stereotype Perceptions of Colorectal Cancer Screening and Diagnosis in the Hispanic Community - Aidan Foley; Bianca Luna-Lupercio; Jessica M. Capaldi; Galen Wiens-Cook; Vinicius Calsavara; Zulfikarali Surani; Sarah-Jeanne Salvy; Jane C. Figueiredo; Robert Haile; Nenette A. Cáceres; Celina H. Shirazipour (Journal of Cancer Education, 2025)
Cancer is a leading cause of death among Hispanic people in the USA. One potential reason is low adherence to cancer screening guidelines, particularly for colorectal cancer (CRC). Previous research suggests that low CRC screening may be linked to negative stereotypes associated with cancer and CRC screening methods. The purpose of this study was to examine explicit stereotype perceptions of CRC screening and diagnosis in the Hispanic community. Hispanic adults ( n = 279) were asked to read three vignettes presenting a gender-neutral individual who was either diagnosed with CRC, completed colonoscopies for CRC screening, or was a control (no cancer information provided). Using the Stereotype Content Model approach, after reading each vignette, participants completed measures assessing explicit perceptions (warmth and competence) of the individual. Linear mixed-effects models were fitted to evaluate differences in perceptions between vignettes. The main effect indicated no significant difference in warmth or competence perceptions based on vignette condition ( p = .78). However, there was a significant difference in explicit perceptions based on the study participant’s Hispanic heritage, gender, and age ( p s < .05). Findings emphasize differences in explicit perceptions of cancer and cancer screening based on important demographic characteristics. Thus, important implications include the need for cancer educational materials and interventions to consider the important heterogeneity within the Hispanic community. Future CRC screening interventions should be tailored based on Hispanic heritage, gender, and age.

Toward a near-lossless image compression strategy for the NASA/USGS Landsat Next mission - Rehman S. Eon; Craig De Groot; Jeffrey A. Pedelty; Aaron Gerace; Matthew Montanaro; Richard K. Covington; Amy S. DeLisa; Wen-Ting Hsieh; Joy M. Henegar-leon; Douglas J. Daniels; Christopher Engebretson; Christopher J. Crawford; et al. (Remote Sensing of Environment, 2025)

Time since HIV diagnosis is linked to amnestic mild cognitive impairment (MCI) in older adults with HIV - Jason S. DeFelice; Mark K. Britton; Yancheng Li; Eric C. Porges; Gladys E. Ibañez; Charurut Somboonwit; Robert L. Cook; Ronald A. Cohen; Joseph M. Gullett (Journal of NeuroVirology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Four unusual mortality events of seabirds in the Patagonian Sea, 2000–2006: species affected and possible causes - Marcela M. Uhart; Ralph E. T. Vanstreels; Flavio Quintana; Belén Mattera; Nora Montoya; Leonardo Guzman; Hernan Pacheco Valles; Gemita Pizarro; Carolina A. Marull; Luciana Pozzi; Torsten Mörner; Pablo García-Borboroglu; et al. (Polar Biology, 2025)
The Patagonian Sea is a highly productive marine ecosystem and a hotspot for seabird diversity and density in the Southwest Atlantic Ocean. Reports of unusual mortality events are relatively scarce in this region, likely due to under detection and investigation. In this study, we report on four unusual mortality events affecting seabirds in the Patagonian Sea from 2000 to 2006. Events 1 and 2 occurred at Golfo Nuevo and Chubut coast, Argentina in September–December 2000, affecting at least 4550 seabirds, mainly Magellanic penguins ( Spheniscus magellanicus ). Event 3 occurred at the Falkland/Malvinas Islands during December 2002–January 2003, affecting at least 3500 seabirds, mainly gentoo penguins ( Pygoscelis papua ). Event 4 occurred at Punta Loma and Punta León, Argentina, in November 2006, affecting at least 57 seabirds, mainly kelp gulls ( Larus dominicanus ). The aetiology of Events 1 and 2 could not be determined, but malnutrition/starvation and paralytic shellfish poisoning, respectively, were identified as potential causes. Pathological findings and toxicological testing supported paralytic shellfish poisoning as the cause of Events 3 and 4. Our results illustrate how identifying the occurrence, cause and extent of unusual mortality events affecting seabirds can present significant challenges. Moreover, our investigations of the events display variations in timeliness and completeness, and our lack of certainty on aetiology reflects the shortcomings often faced in remote locations and low resource settings. Technological advances, such as smartphones, increased public awareness and connectivity, coupled with more and better equipped protected areas and diagnostic laboratories will likely aid in overcoming difficulties from past decades.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Forty-five years of removal campaigns for feral ungulates reveal strategies for success and future directions - Nathan P. Snow; Keely J. Kohen; Ingrid A. Messer; Abigail Pagels; Seth M. Cook; Scott Beckerman; Travis Guerrant; Kurt C. VerCauteren; Kim M. Pepin (Biological Invasions, 2025)
Feral or invasive ungulates (hereafter: feral ungulates) exist worldwide, and their ability to thrive threatens biodiversity, degrades ecosystems, and causes damage to agriculture and properties. Strategies for removing feral ungulates from their introduced insular and mainland ranges have varied greatly, successes have been difficult, and the need is increasing. We reviewed published scientific literature on feral ungulate eradication and maximum control campaigns during 1978–2023 to identify practices that led to greater success. Of 54 campaigns, 32 (59%) reported success. Most campaigns focused on feral swine (61%; Sus scrofa ) or feral goats (24%; Capra hircus ). The average duration of a campaign was 61 months and cost an average of $1.9 m ($USD 2024) or $636/km 2 /month. The most important components for success included ensuring adequate funding was secured for the campaign ($0.5–1 million/km 2 is recommended) and population recovery or reinvasion were minimized. The frequency of campaigns has increased during the last 45 years; however, the areas worked (km 2 ), monthly durations, removal techniques used, funding, and ultimately the rates of success have not changed. A lack of increasing success for larger and more complex campaigns indicated that modernization of technologies for population control has been minimal, and larger breakthroughs are needed. Safe and effective toxicants and sterilants may provide those advances if developed. Lessons learned from campaigns indicate that pilot testing control methods prior to initiating full campaigns may help to alleviate uncertainties, produce more reliable plans, and help inform the biology of the animals being targeted for removal.

Informatics for toxicokinetics - Gilberto Padilla Mercado; Christopher Cook; Norman Adkins; Lucas Albrecht; Grace Cary; Brenda Edwards; Derik E. Haggard; Nancy M. Hanley; Michael F. Hughes; Anna Jarnagin; Tirumala D. Kodavanti; Evgenia Korol-Bexell; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2025)

Correction to: Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2025)

Rhenium-osmium and oxygen isotope homogeneity during the 2022 Mauna Loa eruption and implications for basaltic magma storage - Emily A. Rhoads; Anton Kutyrev; Ilya N. Bindeman; Kendra J. Lynn; Frank A. Trusdell; Drew T. Downs; Hunter R. Edwards; Geoffrey W. Cook; James M. D. Day (Bulletin of Volcanology, 2025)
Mauna Loa is one of the largest and most active volcanoes on Earth. The most recent eruption of Mauna Loa started on 27 November 2022, lasted for 13 days, and was preceded by the longest repose time of 38 years in its modern history. In this contribution, new trace- and highly siderophile-element (HSE: Os, Ir, Ru, Pt, Pd, Re) abundances, 187 Re- 187 Os, and 18 O/ 16 O data are reported for the 2022 lavas. These lavas have a limited range of MgO (6.2 ± 0.1 wt.%) and Ni (83 ± 2 µg/g), with a broader range of Re (0.3 to 1.3 ng/g) and consistent Os (0.031 to 0.080 ng/g) contents. They have 187 Os/ 188 Os ratios (0.1345 to 0.1385) which are, on average, more radiogenic than Mauna Loa picrites (0.1331 to 0.1349) and are similar in composition to more differentiated Mauna Loa tholeiite lavas (0.1340 to 0.1381). The oxygen isotope compositions of glassy samples are 5.35 ± 0.15‰ ( n = 13) and span a range in δ 18 O of + 5.0 to + 5.5‰, with an average composition 0.2 to 0.3‰ lower than MORB. The δD value is − 81 ± 11‰ ( n = 5) at very low (0.03 ± 0.015 wt.%) H 2 O concentrations. The 2022 Mauna Loa eruption is similar in terms of δ 18 O but contrasts in terms of 187 Os/ 188 Os variability, with the recent longer-lived eruptions on La Palma (Canary Islands; 85 days) in 2021 and on the Reykjanes Peninsula (Iceland) that began in 2021 and are still ongoing. Initial lavas were more fractionated for both the Canary Islands and Iceland eruptions, producing more radiogenic Os isotope compositions than later erupted products. The 2022 Mauna Loa eruption showed no such trends. The limited range in isotope compositions of the 2022 Mauna Loa lavas and their strongly fractioned HSE patterns reflect long-term storage, crystal fractionation, and assimilation of related basaltic volcanic edifice materials by the parent magma beneath the volcano prior to eruption triggering. Eruption of differentiated and homogeneous tholeiite lavas at the summit caldera and high on the volcano’s flank, with emplacement of accumulative picrites lower on the volcano, are consistent with neutral buoyancy arguments.

Cross-cultural evidence that intergroup conflict heightens preferences for dominant leaders: A 25-country study - Lasse Laustsen; Xiaotian Sheng; M. Ghufran Ahmad; Laith Al-Shawaf; Benjamin Banai; Irena Pavela Banai; Michael Barlev; Nicolas Bastardoz; Alexander Bor; Joey T. Cheng; Anna Chmielińska; Alexandra Cook; et al. (Evolution and Human Behavior, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Associations between per- and polyfluoroalkyl substances (PFAS) and female sexual function in a preconception cohort - Samantha Schildroth; Julia C. Bond; Amelia K. Wesselink; Jasmine Abrams; Antonia M. Calafat; Julianne Cook Botelho; Katharine O. White; Ganesa Wegienka; Elizabeth E. Hatch; Lauren A. Wise (Environmental Research, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Dietary Fiber Intake and Risk of Advanced and Aggressive Forms of Prostate Cancer: A Pooled Analysis of 15 Prospective Cohort Studies - Elkhansa Sidahmed; Stephen J. Freedland; Molin Wang; Kana Wu; Demetrius Albanes; Matt Barnett; Piet A. van den Brandt; Michael B. Cook; Graham G. Giles; Edward Giovannucci; Christopher A. Haiman; Susanna C. Larsson; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Mechanistic in silico explorations of the immunogenic and synergistic effects of radiotherapy and immunotherapy: a critical review - Allison M. Ng; Kelly M. MacKinnon; Alistair A. Cook; Rebecca A. D’Alonzo; Pejman Rowshanfarzad; Anna K. Nowak; Suki Gill; Martin A. Ebert (Physical and Engineering Sciences in Medicine, 2024)
Immunotherapy is a rapidly evolving field, with many models attempting to describe its impact on the immune system, especially when paired with radiotherapy. Tumor response to this combination involves a complex spatiotemporal dynamic which makes either clinical or pre-clinical in vivo investigation across the resulting extensive solution space extremely difficult. In this review, several in silico models of the interaction between radiotherapy, immunotherapy, and the patient’s immune system are examined. The study included only mathematical models published in English that investigated the effects of radiotherapy on the immune system, or the effect of immuno-radiotherapy with immune checkpoint inhibitors. The findings indicate that treatment efficacy was predicted to improve when both radiotherapy and immunotherapy were administered, compared to radiotherapy or immunotherapy alone. However, the models do not agree on the optimal schedule and fractionation of radiotherapy and immunotherapy. This corresponds to relevant clinical trials, which report an improved treatment efficacy with combination therapy, however, the optimal scheduling varies between clinical trials. This discrepancy between the models can be attributed to the variation in model approach and the specific cancer types modeled, making the determination of the optimum general treatment schedule and model challenging. Further research needs to be conducted with similar data sets to evaluate the best model and treatment schedule for a specific cancer type and stage.

Threat assessment for Pacific sand lance (Ammodytes personatus) in the Salish Sea - Jacqueline R. Huard; Victoria Hemming; Matthew R. Baker; Jennifer Blancard; Ian Bruce; Sarah Cook; Gail K. Davoren; Phillip Dionne; Virginia East; J. Mark Hipfner; Nicola R. Houtman; Brian A. Koval; et al. (Frontiers in Marine Science, 2024)
Like many forage fish species, Pacific sand lance ( Ammodytes personatus ) play a key role in nearshore marine ecosystems as an important prey source for a diverse array of predators in the northeastern Pacific. However, the primary threats to Pacific sand lance and their habitat are poorly defined due to a lack of systematic data. Crucial information needed to assess their population status is also lacking including basic knowledge of their local and regional abundance and distribution. Sand lance are currently listed as ‘not evaluated’ under the IUCN red list and they have not been assessed by US and Canadian agencies. This hampers management and policy efforts focused on their conservation. To address this knowledge gap, we conducted a three-part, structured expert elicitation to assess the vulnerability of Salish Sea sand lance populations. Experts were asked to list and rank key threats to Salish Sea sand lance and/or their habitat, to further quantify the vulnerability of sand lance to identified threats using a vulnerability matrix, and to predict the population trajectory in 25 years from today. Impacts associated with climate change (e.g. sea level rise, sea temperature rise, ocean acidification, and extreme weather) consistently ranked high as threats of concern in the ranking exercise and quantified vulnerability scores. Nearly every expert predicted the population will have declined from current levels in 25 years. These results suggest sand lance face numerous threats and may be in decline under current conditions. This research provides vital information about which threats pose the greatest risk to the long-term health of sand lance populations and their habitat. Managers can use this information to prioritize which threats to address. Future research to reliably quantify population size, better understand the roles of natural and anthropogenic impacts, and to identify the most cost-effective actions to mitigate multiple threats, is recommended.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Oral Bioavailability Enhancement of Poorly Soluble Drug by Amorphous Solid Dispersion Using Sucrose Acetate Isobutyrate - Eman M. Mohamed; Sathish Dharani; Tahir Khuroo; Mohammad T. H. Nutan; Phillip Cook; Rajendran Arunagiri; Mansoor A. Khan; Ziyaur Rahman (AAPS PharmSciTech, 2024)

Spatio-temporal patterns in the biomass, species composition and nitrogen content of drift macroalgae in an urbanised coastal embayment - Juan Manuel Valero-Rodriguez; Tim Dempster; Wei Wen Wong; John A. Lewis; Perran L. M. Cook; Stephen E. Swearer (Journal of Applied Phycology, 2024)
Understanding spatio-temporal variability in the production of drift macroalgae is useful for monitoring and assessing the influence of local anthropogenic nutrient sources on coastal ecosystems. In this study we: (1) assessed how the drift macroalgal community composition and biomass have changed over a 22-year period in Port Phillip Bay (a large coastal embayment in Victoria, Australia); and (2) measured the amount of accumulated nitrogen in drift macroalgae and the contribution of anthropogenic nitrogen sources through isotopic analysis. The surveys revealed little overlap in species composition (<13%) and a significant decrease in standing stock biomass (from 631 to 49 g m -2 ) between surveys (1995/1996 and 2017/2018). This was associated with a high degree of turnover (β-diversity) at the genus level between surveys (mean – 0.53), resulting in distinct communities at all sites, particularly among red algal genera. In addition, the occurrence of ephemeral macroalgal blooms and a semi-perennial mat of the red macroalga Botryocladia sonderi at 10-15 m depth at locations close to nutrient sources indicate drift macroalgae are important nutrient accumulators in the bay. Isotopic analysis revealed a high contribution of anthropogenic-derived nitrogen (δ 15 N > 17‰ and ~ 3% N content) at depths and locations close to nutrient sources, particularly at times of the year when large wastewater discharges occur. Harvesting of drift macroalgae could be a cost-effective solution for offsetting nitrogen inputs from anthropogenic sources, but it will be important to first investigate whether harvesting results in negative impacts to associated fauna or nutrient cycling.

Reframing wildlife disease management problems with decision analysis - Margaret C. McEachran; Johanna A. Harvey; Riley O. Mummah; Molly C. Bletz; Claire S. Teitelbaum; Elias Rosenblatt; F. Javiera Rudolph; Fernando Arce; Shenglai Yin; Diann J. Prosser; Brittany A. Mosher; Jennifer M. Mullinax; et al. (Conservation Biology, 2024)
Contemporary wildlife disease management is complex because managers need to respond to a wide range of stakeholders, multiple uncertainties, and difficult trade‐offs that characterize the interconnected challenges of today. Despite general acknowledgment of these complexities, managing wildlife disease tends to be framed as a scientific problem, in which the major challenge is lack of knowledge. The complex and multifactorial process of decision‐making is collapsed into a scientific endeavor to reduce uncertainty. As a result, contemporary decision‐making may be oversimplified, rely on simple heuristics, and fail to account for the broader legal, social, and economic context in which the decisions are made. Concurrently, scientific research on wildlife disease may be distant from this decision context, resulting in information that may not be directly relevant to the pertinent management questions. We propose reframing wildlife disease management challenges as decision problems and addressing them with decision analytical tools to divide the complex problems into more cognitively manageable elements. In particular, structured decision‐making has the potential to improve the quality, rigor, and transparency of decisions about wildlife disease in a variety of systems. Examples of management of severe acute respiratory syndrome coronavirus 2, white‐nose syndrome, avian influenza, and chytridiomycosis illustrate the most common impediments to decision‐making, including competing objectives, risks, prediction uncertainty, and limited resources.

Association of diet with per- and polyfluoroalkyl substances in plasma and human milk in the New Hampshire Birth Cohort Study - Yuting Wang; Jiang Gui; Caitlin G. Howe; Jennifer A. Emond; Rachel L. Criswell; Lisa G. Gallagher; Carin A. Huset; Lisa A. Peterson; Julianne Cook Botelho; Antonia M. Calafat; Brock Christensen; Margaret R. Karagas; et al. (Science of The Total Environment, 2024)

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

Per- and polyfluoroalkyl substances (PFAS), perceived stress, and depressive symptoms in a prospective cohort study of black women - Samantha Schildroth; Birgit Claus Henn; Anissa I. Vines; Ruth J. Geller; Sharonda M. Lovett; Chad M. Coleman; Traci N. Bethea; Julianne Cook Botelho; Antonia M. Calafat; Chad Milando; Donna D. Baird; Ganesa Wegienka; et al. (Science of The Total Environment, 2024)

Plasma per- and polyfluoroalkyl substance mixtures during pregnancy and duration of breastfeeding in the New Hampshire birth cohort study - Megan E. Romano; Lisa G. Gallagher; George Price; Kathryn A. Crawford; Rachel Criswell; Emily Baker; Julianne Cook Botelho; Antonia M. Calafat; Margaret R. Karagas (International Journal of Hygiene and Environmental Health, 2024)

What is known, unknown, and needed to be known about damage caused by wild pigs - Kurt C. VerCauteren; Kim M. Pepin; Seth M. Cook; Sophie McKee; Abigail Pagels; Keely J. Kohen; Ingrid A. Messer; Michael P. Glow; Nathan P. Snow (Biological Invasions, 2024)
Damage assessments provide evidence for initiating and evaluating management programs that protect natural resources and human livelihoods against invasive species. Wild pigs ( Sus scrofa ) cause extensive damage in their native and non-native ranges, but the extent of current damage and efficacy of management of the damage (i.e., population control of wild pigs, exclusion fencing, etc.) remains poorly described. We conducted a systematic review of physical damage caused by wild pigs to summarize what is known and identify knowledge gaps for damage assessment. Wild pig damage assessments have been overwhelmingly qualitative (84% of studies) and measured differently across studies, which prevents the determination of typical damage amounts to a particular resource and comparison across studies. Key priorities going forward are to standardize damage assessments quantitatively and measure population density (or index of such) of wild pigs concurrently with damage assessments to determine the relationship between damage and population levels. We provide a framework for inferring damage in new areas and assessing the benefits of management—to evaluate and optimize landscape-scale management programs. Overall, we recommend future studies strive for: (1) report the amount of damages in a standardized fashion (e.g., area damaged/area surveyed), (2) evaluate and report the amount of damage relative to the density of wild pigs, and (3) when reporting economic costs of damages incurred and management actions, describe the economic valuation method used along with the year of reference for the valuation. Capturing these elements are necessary steps to predict the benefits of management for an area with particular profile of resources and wild pig density, even in areas where damage assessments are not available. Meeting these criteria with allow for more generalizable results that can inform managers across the nearly global distribution of wild pigs.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Identifying the influence of episodic events on groundwater recharge in semi-arid environments using environmental tracers - M. Chmielarski; S. Dogramaci; P.G. Cook; G. Skrzypek; A. Jackson; M. Nelson Tredwell; J.L. McCallum (Journal of Hydrology, 2024)

Moderate D/H ratios in methane ice on Eris and Makemake as evidence of hydrothermal or metamorphic processes in their interiors: Geochemical analysis - Christopher R. Glein; William M. Grundy; Jonathan I. Lunine; Ian Wong; Silvia Protopapa; Noemi Pinilla-Alonso; John A. Stansberry; Bryan J. Holler; Jason C. Cook; Ana Carolina Souza-Feliciano (Icarus, 2024)

Spatial variation in spawning timing for multi-species Acropora assemblages in the Red Sea - Eslam O. Osman; David J. Suggett; Tamer M. Attalla; Marco Casartelli; Nathan Cook; Islam El-Sadek; Ahmed Gallab; Elizabeth A. Goergen; Neus Garcias-Bonet; Jessica S. Glanz; Pedro Henrique Pereira; Megan Ramirez-Sanchez; et al. (Frontiers in Marine Science, 2024)
Sexual reproduction is a crucial process for reef building coral populations to maximize genetic diversity and recover from large scale disturbances. Mass spawning events by Acropora species represent critical opportunities for populations to persist, and a process that is increasingly exploited to actively restore degraded reefs. However, the timing and predictive capacity of coral spawning throughout the broad thermal and environmental regime of the Red Sea – a region also undergoing significant development and active reef restoration – remains patchy. We, therefore, conducted three parallel reef surveys in the central Red Sea (Al-Fahal Reef, Thuwal - Saudi Arabia) and the eastern (Shushah Island - Saudi Arabia) and western (Hurghada – Egypt) coast of the northern Red Sea. Surveys assessed the gravidity of gonads, spawning timing, alignment with the lunar cycle of 21 Acropora spp. (total n= 572 colonies) around the full moons of April and May 2023. Consistent with past observations, synchronous spawning was observed for Acropora spp. in both the central and northern Red Sea during April and May, respectively. Interestingly, corals spawned on the full moon in both Shushah and Thuwal sites. In contrast, corals in Hurghada were independent of the lunar cycle and spawned 7-9 nights before the full moon in May. By integrating our 2023 observations with the historical spawning events in Hurghada and Thuwal (2002-2022), we found that the deviation of spawning timing from the full moon day was correlated with absolute Sea Surface Temperature (SST) (earlier spawning before the full moon day, lower SST) and warming rate (earlier spawning, more rapid warming) in 6-weeks prior to spawning. As such, temperature pattern is likely one of the primary factors governing gamete release, among other factors, that likely influence spawning day within the lunar month. These correlations between SST metrics and spawning timing suggest a potential framework to predict future Acropora spp. spawning dates. Our observations demonstrate the importance of parallel efforts across borders to collect critical data needed to inform management strategies aimed at conserving and restoring coral reefs in this ecologically diverse region.

Need and vision for global medium-resolution Landsat and Sentinel-2 data products - Volker C. Radeloff; David P. Roy; Michael A. Wulder; Martha Anderson; Bruce Cook; Christopher J. Crawford; Mark Friedl; Feng Gao; Noel Gorelick; Matthew Hansen; Sean Healey; Patrick Hostert; et al. (Remote Sensing of Environment, 2024)

A comparison of methods to detect low levels of Salmonella enterica in surface waters to support antimicrobial resistance surveillance efforts performed in multiple laboratories - Autumn L. Kraft; Jim E. Wells; Jonathan G. Frye; Abasiofiok M. Ibekwe; Lisa M. Durso; Lari Hiott; Cheryl East; Betty R. McConn; Alison M. Franklin; Laura A. Boczek; Jay L. Garland; Claudine Kabera; et al. (Science of The Total Environment, 2023)

Psychometric Properties of Computerized Cognitive Tools and Standard Neuropsychological Tests Used to Assess Sport Concussion: A Systematic Review - Kristin Wilmoth; Benjamin L. Brett; Natalie A. Emmert; Carolyn M. Cook; Jeffrey Schaffert; Todd Caze; Thomas Kotsonis; Margaret Cusick; Gary Solomon; Jacob E. Resch; C. Munro Cullum; Lindsay D. Nelson; et al. (Neuropsychology Review, 2023)

Simulating carbon accumulation and loss in the central Congo peatlands - Dylan M. Young; Andy J. Baird; Paul J. Morris; Greta C. Dargie; Y. Emmanuel Mampouya Wenina; Mackline Mbemba; Arnoud Boom; Peter Cook; Richard Betts; Eleanor Burke; Yannick E. Bocko; Sarah Chadburn; et al. (Global Change Biology, 2023)
Peatlands of the central Congo Basin have accumulated carbon over millennia. They currently store some 29 billion tonnes of carbon in peat. However, our understanding of the controls on peat carbon accumulation and loss and the vulnerability of this stored carbon to climate change is in its infancy. Here we present a new model of tropical peatland development, DigiBog_Congo, that we use to simulate peat carbon accumulation and loss in a rain‐fed interfluvial peatland that began forming ~20,000 calendar years Before Present (cal. yr BP, where ‘present’ is 1950 CE). Overall, the simulated age‐depth curve is in good agreement with palaeoenvironmental reconstructions derived from a peat core at the same location as our model simulation. We find two key controls on long‐term peat accumulation: water at the peat surface (surface wetness) and the very slow anoxic decay of recalcitrant material. Our main simulation shows that between the Late Glacial and early Holocene there were several multidecadal periods where net peat and carbon gain alternated with net loss. Later, a climatic dry phase beginning ~5200 cal. yr BP caused the peatland to become a long‐term carbon source from ~3975 to 900 cal. yr BP. Peat as old as ~7000 cal. yr BP was decomposed before the peatland's surface became wetter again, suggesting that changes in rainfall alone were sufficient to cause a catastrophic loss of peat carbon lasting thousands of years. During this time, 6.4 m of the column of peat was lost, resulting in 57% of the simulated carbon stock being released. Our study provides an approach to understanding the future impact of climate change and potential land‐use change on this vulnerable store of carbon.

Seasonal Rainfall, Shrub Cover and Soil Properties Drive Production of Winter Annuals in the Northern Sonoran Desert - Julea A. Shaw; Scott L. Collins; Timothy J. Ohlert; Hannah Heavenrich; Elizabeth Cook; Megan M. Wheeler; Nancy B. Grimm; Sharon J. Hall (Ecosystems, 2023)

Assessing resilience, equity, and sustainability of future visions across two urban scales - Marta Berbés-Blázquez; Elizabeth M. Cook; Nancy B. Grimm; David M. Iwaniec; Lelani M. Mannetti; Tischa A. Muñoz-Erickson; Darin Wahl (Sustainability Science, 2023)
Cities need to take swift action to deal with the impacts of extreme climate events. The co-production of positive visions offers the potential to not only imagine but also intervene in guiding change toward more desirable urban futures. While participatory visioning continues to be used as a tool for urban planning, there needs to be a way of comparing and evaluating future visions so that they can inform decision-making. Traditional tools for comparison tend to favor quantitative modeling, which is limited in its ability to capture nuances or normative elements of visions. In this paper, we offer a qualitative method to assess the resilience, equity, and sustainability of future urban visions and demonstrate its use by applying it to 11 visions from Phoenix, AZ. The visions were co-produced at two different governance scales: five visions were created at the village (or borough) scale, and six visions were created at the regional (or metropolitan) scale. Our analysis reveals different emphases in the mechanisms present in the visions to advance resilience, sustainability, and equity. In particular, we note that regional future visions align with a green sustainability agenda, whereas village visions focus on social issues and emphasize equity-driven approaches. The visions have implications for future trajectories, and the priorities that manifest at the two scales speak of the political nature of visioning and the need to explore how these processes may interact in complementary, synergistic, or antagonistic ways.

Heat stress survival and thermal tolerance of Australian stingless bees - Scott Nacko; Mark A. Hall; Rosalyn Gloag; Kate E. Lynch; Robert N. Spooner-Hart; James M. Cook; Markus Riegler (Journal of Thermal Biology, 2023)

Development and Validation of an Abbreviated Child and Adult Food Security Scale for Use in Clinical and Research Settings in the United States - Ana Poblacion; Stephanie Ettinger de Cuba; Deborah A. Frank; Georgiana Esteves; Lindsey J. Rateau; Timothy C. Heeren; Sharon Coleman; Maureen M. Black; Diana B. Cutts; Félice Lê-Scherban; Eduardo R. Ochoa; Megan Sandel; et al. (Journal of the Academy of Nutrition and Dietetics, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

The influence of complex matrices on method performance in extracting and monitoring for microplastics - Leah M. Thornton Hampton; Hannah De Frond; Kristine Gesulga; Syd Kotar; Wenjian Lao; Cindy Matuch; Stephen B. Weisberg; Charles S. Wong; Susanne Brander; Silke Christansen; Cayla R. Cook; Fangni Du; et al. (Chemosphere, 2023)

Pulses of labile carbon cause transient decoupling of fermentation and respiration in permeable sediments - Philipp A. Nauer; Adam J. Kessler; Puspitaningsih Hall; Maria Elena Popa; Sophie ten Hietbrink; Tess Hutchinson; Wei Wen Wong; Karl Attard; Ronnie N. Glud; Chris Greening; Perran L. M. Cook (Limnology and Oceanography, 2023)
Dihydrogen (H 2 ) is an important intermediate in anaerobic microbial processes, and concentrations are tightly controlled by thermodynamic limits of consumption and production. However, recent studies reported unusual H 2 accumulation in permeable marine sediments under anoxic conditions, suggesting decoupling of fermentation and sulfate reduction, the dominant respiratory process in anoxic permeable marine sediments. Yet, the extent, prevalence and potential triggers for such H 2 accumulation and decoupling remain unknown. We surveyed H 2 concentrations in situ at different settings of permeable sand and found that H 2 accumulation was only observed during a coral spawning event on the Great Barrier Reef. A flume experiment with organic matter addition to the water column showed a rapid accumulation of hydrogen within the sediment. Laboratory experiments were used to explore the effect of oxygen exposure, physical disturbance and organic matter inputs on H 2 accumulation. Oxygen exposure had little effect on H 2 accumulation in permeable sediments suggesting both fermenters and sulfate reducers survive and rapidly resume activity after exposure to oxygen. Mild physical disturbance mimicking sediment resuspension had little effect on H 2 accumulation; however, vigorous shaking led to a transient accumulation of H 2 and release of dissolved organic carbon suggesting mechanical disturbance and cell destruction led to organic matter release and transient decoupling of fermenters and sulfate reducers. In summary, the highly dynamic nature of permeable sediments and its microbial community allows for rapid but transient decoupling of fermentation and respiration after a C pulse, leading to high H 2 levels in the sediment.

Coral assemblages at higher latitudes favor short‐term potential over long‐term performance - James Cant; James D. Reimer; Brigitte Sommer; Katie M. Cook; Sun W. Kim; Carrie A. Sims; Takuma Mezaki; Cliodhna O'Flaherty; Maxime Brooks; Hamish A. Malcolm; John M. Pandolfi; Roberto Salguero‐Gómez; et al. (Ecology, 2023)
The persistent exposure of coral assemblages to more variable abiotic regimes is assumed to augment their resilience to future climatic variability. Yet, while the determinants of coral population resilience across species remain unknown, we are unable to predict the winners and losers across reef ecosystems exposed to increasingly variable conditions. Using annual surveys of 3171 coral individuals across Australia and Japan (2016–2019), we explore spatial variation across the short‐ and long‐term dynamics of competitive, stress‐tolerant, and weedy assemblages to evaluate how abiotic variability mediates the structural composition of coral assemblages. We illustrate how, by promoting short‐term potential over long‐term performance, coral assemblages can reduce their vulnerability to stochastic environments. However, compared to stress‐tolerant, and weedy assemblages, competitive coral taxa display a reduced capacity for elevating their short‐term potential. Accordingly, future climatic shifts threaten the structural complexity of coral assemblages in variable environments, emulating the degradation expected across global tropical reefs.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Ancient bears provide insights into Pleistocene ice age refugia in Southeast Alaska - Flavio Augusto da Silva Coelho; Stephanie Gill; Crystal M. Tomlin; Marilena Papavassiliou; Sean D. Farley; Joseph A. Cook; Sarah A. Sonsthagen; George K. Sage; Timothy H. Heaton; Sandra L. Talbot; Charlotte Lindqvist (Molecular Ecology, 2023)
During the Late Pleistocene, major parts of North America were periodically covered by ice sheets. However, there are still questions about whether ice‐free refugia were present in the Alexander Archipelago along the Southeast (SE) Alaska coast during the last glacial maximum (LGM). Numerous subfossils have been recovered from caves in SE Alaska, including American black ( Ursus americanus ) and brown ( U. arctos ) bears, which today are found in the Alexander Archipelago but are genetically distinct from mainland bear populations. Hence, these bear species offer an ideal system to investigate long‐term occupation, potential refugial survival and lineage turnover. Here, we present genetic analyses based on 99 new complete mitochondrial genomes from ancient and modern brown and black bears spanning the last ~45,000 years. Black bears form two SE Alaskan subclades, one preglacial and another postglacial, that diverged >100,000 years ago. All postglacial ancient brown bears are closely related to modern brown bears in the archipelago, while a single preglacial brown bear is found in a distantly related clade. A hiatus in the bear subfossil record around the LGM and the deep split of their pre‐ and postglacial subclades fail to support a hypothesis of continuous occupancy in SE Alaska throughout the LGM for either species. Our results are consistent with an absence of refugia along the SE Alaska coast, but indicate that vegetation quickly expanded after deglaciation, allowing bears to recolonize the area after a short‐lived LGM peak.

Late Cenozoic history and the role of Beringia in assembling a Holarctic cestode species complex - Kurt E. Galbreath; Arseny A. Makarikov; Kayce C. Bell; Stephen E. Greiman; Julie M. Allen; Genevieve M.S. Haas; Chenhong Li; Joseph A. Cook; Eric P. Hoberg (Molecular Phylogenetics and Evolution, 2023)

Microbial diversity in stingless bee gut is linked to host wing size and influenced by the environment - Hongwei Liu; Mark A. Hall; Laura E. Brettell; Juntao Wang; Megan Halcroft; Scott Nacko; Robert Spooner-Hart; James M. Cook; Markus Riegler; Brajesh K. Singh (Journal of Invertebrate Pathology, 2023)

Total thermal neutron cross section measurements of hydrogen dense polymers from 0.0005–20 eV - D. Fritz; Y. Danon; K. Ramic; C.W. Chapman; J.M. Brown; G. Arbanas; M. Rapp; T.H. Trumbull; M. Zerkle; J. Holmes; P. Brain; A. Ney; et al. (Annals of Nuclear Energy, 2023)

SCAview: an Intuitive Visual Approach to the Integrative Analysis of Clinical Data in Spinocerebellar Ataxias - Mischa Uebachs; Philipp Wegner; Sebastian Schaaf; Simon Kugai; Heike Jacobi; Sheng-Han Kuo; Tetsuo Ashizawa; Juliane Fluck; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; Arron Cook; et al. (The Cerebellum, 2023)
With SCAview, we present a prompt and comprehensive tool that enables scientists to browse large datasets of the most common spinocerebellar ataxias intuitively and without technical effort. Basic concept is a visualization of data, with a graphical handling and filtering to select and define subgroups and their comparison. Several plot types to visualize all data points resulting from the selected attributes are provided. The underlying synthetic cohort is based on clinical data from five different European and US longitudinal multicenter cohorts in spinocerebellar ataxia type 1, 2, 3, and 6 (SCA1, 2, 3, and 6) comprising > 1400 patients with overall > 5500 visits. First, we developed a common data model to integrate the clinical, demographic, and characterizing data of each source cohort. Second, the available datasets from each cohort were mapped onto the data model. Third, we created a synthetic cohort based on the cleaned dataset. With SCAview, we demonstrate the feasibility of mapping cohort data from different sources onto a common data model. The resulting browser-based visualization tool with a thoroughly graphical handling of the data offers researchers the unique possibility to visualize relationships and distributions of clinical data, to define subgroups and to further investigate them without any technical effort. Access to SCAview can be requested via the Ataxia Global Initiative and is free of charge.

Assessing the Effects of Physical Barriers and Hypoxia on Red Drum Movement Patterns to Develop More Effective Management Strategies - Steven M. Baker; Eric A. Reyier; Bonnie J. Ahr; Geoffrey S. Cook (Fishes, 2023)
Human modification of coastal ecosystems often creates barriers to fish movement. Passive acoustic telemetry was used to quantify movement patterns and habitat use of red drums (Sciaenops ocellatus) within and around a complex of coastal impoundments, and explored how the presence of artificial structures (i.e., bollards and culverts) and a hypoxia-related mortality event impacted fish movement. Results indicated bollards impede the movement of individuals with head widths greater than the mean distance between bollards (~16.0 cm). Red drum home range area and daily distance traveled were related to water dissolved oxygen concentrations; as oxygen levels decreased, fish habitat use area decreased initially. However, continued exposure to hypoxic conditions increased fish cumulative daily distance traveled. When exposed to anoxic waters, fish daily distance traveled and rate of movement were greatly reduced. These findings suggest prolonged exposure to low dissolved oxygen in combination with artificial structures can reduce movement of red drum, increase risk of mortality, and decrease habitat connectivity. Constructing and maintaining (sediment and biofouling removal) larger culvert openings and/or using wider bollard spacing would improve water circulation in impoundments, increase habitat connectivity, and facilitate movement of large sportfish inhabiting Florida’s coastal waters.

Total thermal neutron cross section measurements of yttrium hydride from 0.0005 - 3 eV - D. Fritz; Y. Danon; M. Rapp; T.H. Trumbull; M. Zerkle; J. Holmes; C.W. Chapman; G. Arbanas; J.M. Brown; K. Ramic; X. Hu; S. Singh; et al. (Annals of Nuclear Energy, 2023)

The Diversity of Eucheumatoid Seaweed Cultivars in the Philippines - Richard V. Dumilag; Bea A. Crisostomo; Zae-Zae A. Aguinaldo; Lourie Ann R. Hinaloc; Lawrence M. Liao; Hilly Ann Roa-Quiaoit; Floredel Dangan-Galon; Giuseppe C. Zuccarello; Marie-Laure Guillemin; Juliet Brodie; Elizabeth J. Cottier-Cook; Michael Y. Roleda (Reviews in Fisheries Science & Aquaculture, 2023)

Analysis of Charon’s spectrum at 2.21- μ m from New Horizons/LEISA and Earth-based observations - Jason C. Cook; Silvia Protopapa; Cristina M. Dalle Ore; Dale P. Cruikshank; William M. Grundy; Carey M. Lisse; Bernard Schmitt; Anne Verbiscer; Kelsi N. Singer; John Spencer; S. Alan Stern; Harold A. Weaver (Icarus, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Inconsistent results from trait-based analyses of moth trends point to complex drivers of change - George M. Tordoff; Emily B. Dennis; Richard Fox; Patrick M. Cook; Tony M. Davis; Dan Blumgart; Nigel A. D. Bourn (Biodiversity and Conservation, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

The Open-Ocean Gulf of Mexico After Deepwater Horizon: Synthesis of a Decade of Research - Tracey T. Sutton; Rosanna J. Milligan; Kendra Daly; Kevin M. Boswell; April B. Cook; Maëlle Cornic; Tamara Frank; Kaitlin Frasier; Daniel Hahn; Frank Hernandez; John Hildebrand; Chuanmin Hu; et al. (Frontiers in Marine Science, 2022)
The scale of the Deepwater Horizon disaster was and is unprecedented: geographic extent, pollutant amount, countermeasure scope, and of most relevance to this Research Topic issue, range of ecotypes affected. These ecotypes include coastal/nearshore, continental shelf, deep benthic, and open-ocean domains, the last of which is the subject of this synthesis. The open-ocean ecotype comprises ~90% of the volume of the Gulf of Mexico. The exact percentage of this ecotype contaminated with toxins is unknown due to its three-dimensional nature and dynamics, but estimates suggest that the footprint encompassed most of its eastern half. Further, interactions between the water column and the deep benthos may be persistent, making this synthesis one of time (a decade) rather than event conclusion. Here we examine key elements of the open-ocean ecosystem, with emphasis on vulnerability and resilience. Of paramount importance relative to the Gulf nearshore and shelf ecotypes, pre-disaster baseline data were lacking for most of the fauna. In such cases, inferences were drawn from post-disaster assessments. Both phytoplankton and mesozooplankton vulnerabilities were quite high, but resilience appeared equally so. The phytoplankton situation was a bit more complex in that toxin-imposed reductions may have been offset by nutrient injection via high freshwater discharge in 2010. Intermediate trophic levels exhibited population-level depressions, ostensibly due to high vulnerability and low resilience. Apex predator impacts were variable. Certain large epipelagic fishes may have avoided the highest concentrations of hydrocarbons/dispersant, and thus larval abundances returned to pre-disaster levels of variability and abundance within a few years after a steep initial decline. Oceanic cetaceans, particularly shallow-diving stenellid dolphins, did not appear to avoid oiled waters and exhibited strong declines in the northern Gulf. Given that population declines of many open-ocean taxa appear to be ongoing a decade later, we conclude that this largest of Gulf ecosystem components, like its deep-benthic counterpart, is as fragile as it is voluminous. This is particularly concerning given the rapid, and likely irreversible, shift to deeper waters by the US and Mexican oil industries in concert with the higher likelihood of accidents with increasing platform depth.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Rapid radiation of Southern Ocean shags in response to receding sea ice - Nicolas J. Rawlence; Alexander T. Salis; Hamish G. Spencer; Jonathan M. Waters; Lachie Scarsbrook; Kieren J. Mitchell; Richard A. Phillips; Luciano Calderón; Timothée R. Cook; Charles‐André Bost; Ludovic Dutoit; Tania M. King; et al. (Journal of Biogeography, 2022)
Aim Understanding how natural populations respond to climatic shifts is a fundamental goal of biological research in a fast‐changing world. The Southern Ocean represents a fascinating system for assessing large‐scale climate‐driven biological change, as it contains extremely isolated island groups within a predominantly westerly, circumpolar wind and current system. Blue‐eyed shags represent a paradoxical seabird radiation—a circumpolar distribution implies strong dispersal capacity yet their species‐rich nature suggests local adaptation and isolation. Here we attempt to resolve this paradox in light of the history of repeated cycles of climate change in the Southern Ocean. Location Southern Ocean. Taxa 16 species and subspecies of blue‐eyed shags (Phalacrocoracidae; Leucocarbo spp.). Methods We use mitochondrial and nuclear sequence data from individuals across the geographical range of the genus to conduct the first comprehensive, time‐calibrated phylogenetic analyses and ancestral‐range biogeographical reconstructions of the blue‐eyed shags. Results The origins of many island‐endemic lineages are remarkably recent, consistent with a recent high‐latitude circumpolar radiation in the Pliocene or Early Pleistocene. This recent sub‐Antarctic expansion contrasts with significantly deeper lineages detected in South America and, to a lesser extent, New Zealand. These regions, particularly South America, acted as glacial refugia and sources for multiple waves of post‐glacial dispersal. Main conclusions The blue‐eyed shag paradox is resolved, with at least two waves of dispersal, linked to interglacial cycles, explaining the current distribution and diversity. Descendants of a Pliocene or Early Pleistocene wave of dispersal out of South America survive in the New Zealand region. In contrast, taxa distributed on sub‐Antarctic islands originated much later, possibly since the Last Glacial Maximum. Blue‐eyed shags therefore represent a powerful model system—comprising several natural replicates—for studying the early stages of founder‐event speciation and adaptation in a Southern‐Ocean bird group.

Traits data for the butterflies and macro‐moths of Great Britain and Ireland - Patrick M. Cook; George M. Tordoff; Tony M. Davis; Mark S. Parsons; Emily B. Dennis; Richard Fox; Marc S. Botham; Nigel A. D. Bourn (Ecology, 2022)
Butterflies and moths, collectively Lepidoptera, are integral components of ecosystems, providing key services such as pollination and a prey resource for vertebrate and invertebrate predators. Lepidoptera are a relatively well studied group of invertebrates. In Great Britain and Ireland numerous citizen science projects provide data on changes in distribution and abundance. The availability of high‐quality monitoring and recording data, combined with the rapid response of Lepidoptera to environmental change, makes them ideal candidates for traits‐based ecological studies. Recently, there has been an increase in the number of studies documenting traits‐based responses of Lepidoptera, highlighting the demand for a standardized and referenced traits database. There is a wide range of primary and secondary literature sources available regarding the ecology of British and Irish Lepidoptera to support such studies. Currently these sources have not been collated into one central repository that would facilitate and enhance future research. Here, we present a comprehensive traits database for the butterflies and macro‐moths of Great Britain and Ireland. The database covers 968 species in 21 families. Ecological traits fall into four main categories: life cycle ecology and phenology, host plant specificity and characteristics, breeding habitat, and morphological characteristics. The database also contains data regarding species distribution, conservation status, and temporal trends for abundance and occupancy. This database can be used for a wide array of purposes including further fundamental research on species and community responses to environmental change, conservation and management studies, and evolutionary biology. There are no copyright restrictions, and this paper must be cited if data are used in publications.

Local adaptation and spatiotemporal patterns of genetic diversity revealed by repeated sampling of Caenorhabditis elegans across the Hawaiian Islands - Timothy A. Crombie; Paul Battlay; Robyn E. Tanny; Kathryn S. Evans; Claire M. Buchanan; Daniel E. Cook; Clayton M. Dilks; Loraina A. Stinson; Stefan Zdraljevic; Gaotian Zhang; Nicole M. Roberto; Daehan Lee; et al. (Molecular Ecology, 2022)
The nematode Caenorhabditis elegans is among the most widely studied organisms, but relatively little is known about its natural ecology. Genetic diversity is low across much of the globe but high in the Hawaiian Islands and across the Pacific Rim. To characterize the niche and genetic diversity of C. elegans on the Hawaiian Islands and to explore how genetic diversity might be influenced by local adaptation, we repeatedly sampled nematodes over a three‐year period, measured various environmental parameters at each sampling site, and whole‐genome sequenced the C. elegans isolates that we identified. We found that the typical Hawaiian C. elegans niche comprises moderately moist native forests at high elevations (500–1,500 m) where ambient air temperatures are cool (15–20°C). Compared to other Caenorhabditis species found on the Hawaiian Islands ( e.g ., Caenorhabditis briggsae and Caenorhabditis tropicalis ), we found that C. elegans were enriched in native habitats. We measured levels of genetic diversity and differentiation among Hawaiian C. elegans and found evidence of seven genetically distinct groups distributed across the islands. Then, we scanned these genomes for signatures of local adaptation and identified 18 distinct regions that overlap with hyper‐divergent regions, which may be maintained by balancing selection and are enriched for genes related to environmental sensing, xenobiotic detoxification, and pathogen resistance. These results provide strong evidence of local adaptation among Hawaiian C. elegans and contribute to our understanding of the forces that shape genetic diversity on the most remote volcanic archipelago in the world.

The Alberta moving beyond breast cancer (AMBER) cohort study: baseline description of the full cohort - Christine M. Friedenreich; Jeff K. Vallance; Margaret L. McNeely; S. Nicole Culos-Reed; Charles E. Matthews; Gordon J. Bell; John R. Mackey; Karen A. Kopciuk; Leanne Dickau; Qinggang Wang; Diane Cook; Stephanie Wharton; et al. (Cancer Causes & Control, 2022)
Purpose The Alberta Moving Beyond B r east Cancer (AMBER) Study is an ongoing prospective cohort study investigating how direct measures of physical activity (PA), sedentary behavior (SB), and health-related fitness (HRF) are associated with survival after breast cancer. Methods Women in Alberta with newly diagnosed stage I (≥ T1c) to IIIc breast cancer were recruited between 2012 and 2019. Baseline assessments were completed within 90 days of surgery. Measurements included accelerometers to measure PA and SB; a graded treadmill test with gas exchange analysis to measure cardiorespiratory fitness (VO 2peak ); upper and lower body muscular strength and endurance; dual-X-ray absorptiometry to measure body composition; and questionnaires to measure self-reported PA and SB. Results At baseline, the 1528 participants’ mean age was 56 ± 11 years, 59% were post-menopausal, 62% had overweight/obesity, and 55% were diagnosed with stage II or III disease. Based on device measurements, study participants spent 8.9 ± 1.7 h/day sedentary, 4.4 ± 1.2 h/day in light-intensity activity, 0.9 ± 0.5 h/day in moderate-intensity activity, and 0.2 ± 0.2 h/day in vigorous-intensity activity. For those participants who reached VO 2peak , the average aerobic fitness level was 26.6 ± 6 ml/kg/min. Average body fat was 43 ± 7.1%. Conclusion We have established a unique cohort of breast cancer survivors with a wealth of data on PA, SB, and HRF obtained through both direct and self-reported measurements. Study participants are being followed for at least ten years to assess all outcomes after breast cancer. These data will inform clinical and public health guidelines on PA, SB, and HRF for improving breast cancer outcomes.

Prioritization and thresholds for managing biological invasions in urban ecosystems - L. J. Potgieter; M. F. J. Aronson; A. J. Brandt; C. N. Cook; M. Gaertner; N. E. Mandrak; D. M. Richardson; N. Shrestha; M. W. Cadotte (Urban Ecosystems, 2022)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Small artificial waterbodies are widespread and persistent emitters of methane and carbon dioxide - M. Peacock; J. Audet; D. Bastviken; S. Cook; C. D. Evans; A. Grinham; M. A. Holgerson; L. Högbom; A. E. Pickard; P. Zieliński; M. N. Futter (Global Change Biology, 2021)
Inland waters play an active role in the global carbon cycle and emit large volumes of the greenhouse gases (GHGs), methane (CH 4 ) and carbon dioxide (CO 2 ). A considerable body of research has improved emissions estimates from lakes, reservoirs and rivers but recent attention has been drawn to the importance of small, artificial waterbodies as poorly quantified but potentially important emission hotspots. Of particular interest are emissions from drainage ditches and constructed ponds. These waterbody types are prevalent in many landscapes and their cumulative surface areas can be substantial. Furthermore, GHG emissions from constructed waterbodies are anthropogenic in origin and form part of national emissions reporting, whereas emissions from natural waterbodies do not (according to Intergovernmental Panel on Climate Change guidelines). Here, we present GHG data from two complementary studies covering a range of land uses. In the first, we measured emissions from nine ponds and seven ditches over a full year. Annual emissions varied considerably: 0.1–44.3 g CH 4 m −2 year −1 and −36–4421 g CO 2 m −2 year −1 . In the second, we measured GHG concentrations in 96 ponds and 64 ditches across seven countries, covering subtropical, temperate and sub‐arctic biomes. When CH 4 emissions were converted to CO 2 equivalents, 93% of waterbodies were GHG sources. In both studies, GHGs were positively related to nutrient status (C, N, P), and pond GHG concentrations were highest in smallest waterbodies. Ditch and pond emissions were larger per unit area when compared to equivalent natural systems (streams, natural ponds). We show that GHG emissions from natural systems should not be used as proxies for those from artificial waterbodies, and that artificial waterbodies have the potential to make a substantial but largely unquantified contribution to emissions from the Agriculture, Forestry and Other Land Use sector, and the global carbon cycle.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Synergistic antihyperalgesic and antinociceptive effects of morphine and methyl 8-ethynyl-6-(pyridin-2-yl)-4H-benzo[f]imidazo[1,5-a][1,4]diazepine-3-carboxylate (MP-III-024): a positive allosteric modulator at α2GABAA and α3GABAA receptors - Mohammad A. Rahman; Thomas M. Keck; Michael M. Poe; Dishary Sharmin; James M. Cook; Bradford D. Fischer (Psychopharmacology, 2021)

Coating characterization by hyperspectroscopy and predictive dissolution models of tablets coated with blends of cellulose acetate and cellulose acetate phthalate - Tahir Khuroo; Eman M. Mohamed; Sathish Dharani; Hamideh Afrooz; Sogra F. Barakh Ali; Phillip Cook; Mansoor A. Khan; Ziyaur Rahman (AAPS PharmSciTech, 2021)

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Characteristics of Transgender Patient Cases Managed by a Toxicologist: an Analysis of the Toxicology Investigator’s Consortium (ToxIC) Registry: January 2017–June 2019 - Ryan M. Surmaitis; Marna Rayl Greenberg; Natalie E. Ebeling-Koning; Phillip M. Grenz; Cody R. McWhirter; Beth A. Careyva; Judith N. Sabino; Matthew D. Cook; Robert D. Cannon; Andrew L. Koons; Kenneth D. Katz; Hope Kincaid; et al. (Journal of Medical Toxicology, 2021)

Associations between daily aspirin use and cancer risk across strata of major cancer risk factors in two large U.S. cohorts - Lauren M. Hurwitz; Kara A. Michels; Michael B. Cook; Ruth M. Pfeiffer; Britton Trabert (Cancer Causes & Control, 2021)

A Multidisciplinary Approach to Investigate Deep-Pelagic Ecosystem Dynamics in the Gulf of Mexico Following Deepwater Horizon - April B. Cook; Andrea M. Bernard; Kevin M. Boswell; Heather Bracken-Grissom; Marta D’Elia; Sergio deRada; Cole G. Easson; David English; Ron I. Eytan; Tamara Frank; Chuanmin Hu; Matthew W. Johnston; et al. (Frontiers in Marine Science, 2020)
The pelagic Gulf of Mexico (GoM) is a complex system of dynamic physical oceanography (western boundary current, mesoscale eddies), high biological diversity, and community integration via diel vertical migration and lateral advection. Humans also heavily utilize this system, including its deep-sea components, for resource extraction, shipping, tourism, and other commercial activity. This utilization has had impacts, some with disastrous consequences. The Deepwater Horizon oil spill (DWHOS) occurred at a depth of ∼1500 m (Macondo wellhead), creating a persistent and toxic mixture of hydrocarbons and dispersant in the deep-pelagic (water column below 200 m depth) habitat. In order to assess the impacts of the DWHOS on this habitat, two large-scale research programs, described herein, were designed and executed. These programs, ONSAP and DEEPEND, aimed to quantitatively characterize the oceanic ecosystem of the northern GoM and to establish a time-series with which natural and anthropogenic changes could be detected. The approach was multi-disciplinary in nature and included in situ sampling, acoustic sensing, water column profiling and sampling, satellite remote sensing, AUV sensing, numerical modeling, genetic sequencing, and biogeochemical analyses. The synergy of these methodologies has provided new and unprecedented perspectives of an oceanic ecosystem with respect to composition, connectivity, drivers, and variability.

Seasonality of biological and physical systems as indicators of climatic variation and change - Jake F. Weltzin; Julio L. Betancourt; Benjamin I. Cook; Theresa M. Crimmins; Carolyn A. F. Enquist; Michael D. Gerst; John E. Gross; Geoffrey M. Henebry; Rebecca A. Hufft; Melissa A. Kenney; John S. Kimball; Bradley C. Reed; et al. (Climatic Change, 2020)

A little SNP of this, a little SNP of that: The discovery of 116 single nucleotide polymorphism markers to enable the rapid identification of individual Pacific walrus (Odobenus rosmarus divergens) - Geoffrey M. Cook; Daniel J. Prince; Sean M. O’Rourke; Timothy L. King; Michael R. Miller; Cara J. Lewis; Michael S. Eackles; Patrick R. Lemons; Suresh A. Sethi; Jeffrey B. Olsen; John K. Wenburg (Conservation Genetics Resources, 2020)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Genomic analysis of Caldalkalibacillus thermarum TA2.A1 reveals aerobic alkaliphilic metabolism and evolutionary hallmarks linking alkaliphilic bacteria and plant life - Samuel I. de Jong; Marcel A. van den Broek; Alexander Y. Merkel; Pilar de la Torre Cortes; Falk Kalamorz; Gregory M. Cook; Mark C. M. van Loosdrecht; Duncan G. G. McMillan (Extremophiles, 2020)
The aerobic thermoalkaliphile Caldalkalibacillus thermarum strain TA2.A1 is a member of a separate order of alkaliphilic bacteria closely related to the Bacillales order. Efforts to relate the genomic information of this evolutionary ancient organism to environmental adaptation have been thwarted by the inability to construct a complete genome. The existing draft genome is highly fragmented due to repetitive regions, and gaps between and over repetitive regions were unbridgeable. To address this, Oxford Nanopore Technology’s MinION allowed us to span these repeats through long reads, with over 6000-fold coverage. This resulted in a single 3.34 Mb circular chromosome. The profile of transporters and central metabolism gives insight into why the organism prefers glutamate over sucrose as carbon source. We propose that the deamination of glutamate allows alkalization of the immediate environment, an excellent example of how an extremophile modulates environmental conditions to suit its own requirements. Curiously, plant-like hallmark electron transfer enzymes and transporters are found throughout the genome, such as a cytochrome b 6 c 1 complex and a CO 2 -concentrating transporter. In addition, multiple self-splicing group II intron-encoded proteins closely aligning to those of a telomerase reverse transcriptase in Arabidopsis thaliana were revealed. Collectively, these features suggest an evolutionary relationship to plant life.

Taxon pulse dynamics, episodic dispersal and host colonization across Beringia drive diversification of a Holarctic tapeworm assemblage - Genevieve M. S. Haas; Eric P. Hoberg; Joseph A. Cook; Heikki Henttonen; Arseny A. Makarikov; Sarah R. Gallagher; Nikolai E. Dokuchaev; Kurt E. Galbreath (Journal of Biogeography, 2020)
Aim We test the predictions of the Stockholm Paradigm, a synthesis of eco‐evolutionary theory explaining the nature of faunal assembly, host range and parasite diversification. Faunal diversification and assembly, manifested in patterns of host colonization, co‐adaptation and parasite speciation, are predicted to emerge as a consequence of alternating episodes of ecological disruption and stability. Specifically, for a diverse cestode genus ( Arostrilepis ), we evaluate the number and direction of Pleistocene dispersal events across Beringia, the number and relative timing of host colonization events and the relationship between host and parasite biogeographic histories and associations through time. Location Beringia and adjacent temperate to arctic biomes in North America and Eurasia. Taxon Arostrilepis (Cyclophyllidea: Hymenolepididae) and its rodent hosts. Methods Multi‐locus phylogenetic reconstruction and biogeographic ancestral range estimation. Results Arostrilepis lineages crossed Beringia eastward into North America a minimum of four times and westward into Asia twice in association with temporally disjunct geographic expansions of three major tribes of cricetid rodents (Arvicolini, Myodini, Lemmini). Inferences of ancestral host associations support at least nine instances of host colonization involving shifts from one rodent tribe or family to another. Several previously unrecognized lineages of Arostrilepis are revealed. Main conclusions Consistent with expectations of the Stockholm Paradigm, episodes of intercontinental dispersal were both frequent in the history of Arostrilepis and preceded a majority of inferred host‐colonization events. Events of historical geographic expansion created numerous opportunities for development of novel host–parasite associations through ecological fitting, as parasites tracked historically conserved resources available across diverse host taxa. Beringia played a major role in shaping rodent/parasite assemblages by mediating dispersal between the northern continents during glacial episodes of the Pleistocene, rather than by serving as a zone of refugial isolation.

S-EQUOL: a neuroprotective therapeutic for chronic neurocognitive impairments in pediatric HIV - Kristen A. McLaurin; Hailong Li; Anna K. Cook; Rosemarie M. Booze; Charles F. Mactutus (Journal of NeuroVirology, 2020)

An analysis of the current status and future of biosecurity frameworks for the Indonesian seaweed industry - Cicilia S. B. Kambey; Iona Campbell; Calvyn F. A. Sondak; Adibi R. M. Nor; Phaik E. Lim; Elizabeth J. Cottier-Cook (Journal of Applied Phycology, 2020)
Indonesia is the world largest producer of the red seaweeds Kappaphycus and Eucheuma ; however, this country is facing significant challenges such as disease outbreaks, epiphyte infestations and a loss in seedling quality. Biosecurity practices have been widely adopted in other aquaculture sectors and when enforced can help to limit the introduction and spread of diseases and pests. To assess current capacity for biosecurity in seaweed aquaculture in Indonesia, a systematic analysis of policy frameworks including legislation, regulatory tools, and national standards was conducted. Biosecurity themes and risks were used to evaluate current national biosecurity content. The results identified major challenges faced by the industry in order to implement biosecurity policies in practice. Barriers to implementation included unspecific reference to the seaweed aquaculture sector, limited variety of approaches to biosecurity, limited use of up-to-date scientific evidence, insufficient guidance for the use of precaution and insufficient inclusion of specific biosecurity hazards. In general, although national regulations are currently under revision, current policies indicate a lack of clarity where biosecurity is included. Six recommendations are suggested to incorporate proactive biosecurity actions into current frameworks, with the aim of improving the health and sustainability of the seaweed aquaculture sector in Indonesia.

Fitness, independent of physical activity is associated with cerebral blood flow in adults at risk for Alzheimer’s disease - Ryan J. Dougherty; Elizabeth A. Boots; Jacob B. Lindheimer; Aaron J. Stegner; Stephanie Van Riper; Dorothy F. Edwards; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; Sanjay Asthana; Bruce P. Hermann; et al. (Brain Imaging and Behavior, 2020)

Simulating alternative sustainable water futures - D. A. Sampson; E. M. Cook; M. J. Davidson; N. B. Grimm; D. M. Iwaniec (Sustainability Science, 2020)

Development of Abuse-Deterrent Formulations Using Sucrose Acetate Isobutyrate - Sogra F. Barakh Ali; Sathish Dharani; Hamideh Afrooz; Eman M. Mohamed; Phillip Cook; Mansoor A. Khan; Ziyaur Rahman (AAPS PharmSciTech, 2020)

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

Development of an instrumented thoracoscopic surgical trainer for objective evaluation of esophageal atresia/tracheoesophageal fistula repair - Ashton A. Moorhead; David Nair; Chris Morison; Nicholas J. Cook; Spencer W. Beasley; Jonathan M. Wells (Medical & Biological Engineering & Computing, 2020)

The Vertical and Horizontal Distribution of Deep-Sea Crustaceans in the Order Euphausiacea in the Vicinity of the DeepWater Horizon Oil Spill - Tamara M. Frank; Charles D. Fine; Eric A. Burdett; April B. Cook; Tracey T. Sutton (Frontiers in Marine Science, 2020)

Ultra-endurance triathlon performance and markers of whole-body and gut-specific inflammation - Kyle A. Smith; Jacob N. Kisiolek; Brandon D. Willingham; Margaret C. Morrissey; Samantha M. Leyh; Patrick G. Saracino; Daniel A. Baur; Marc D. Cook; Michael J. Ormsbee (European Journal of Applied Physiology, 2020)

The global Microcystis interactome - Katherine V. Cook; Chuang Li; Haiyuan Cai; Lee R. Krumholz; K. David Hambright; Hans W. Paerl; Morgan M. Steffen; Alan E. Wilson; Michele A. Burford; Hans‐Peter Grossart; David P. Hamilton; Helong Jiang; et al. (Limnology and Oceanography, 2020)
Bacteria play key roles in the function and diversity of aquatic systems, but aside from study of specific bloom systems, little is known about the diversity or biogeography of bacteria associated with harmful cyanobacterial blooms (cyanoHABs). CyanoHAB species are known to shape bacterial community composition and to rely on functions provided by the associated bacteria, leading to the hypothesized cyanoHAB interactome, a coevolved community of synergistic and interacting bacteria species, each necessary for the success of the others. Here, we surveyed the microbiome associated with Microcystis aeruginosa during blooms in 12 lakes spanning four continents as an initial test of the hypothesized Microcystis interactome. We predicted that microbiome composition and functional potential would be similar across blooms globally. Our results, as revealed by 16S rRNA sequence similarity, indicate that M. aeruginosa is cosmopolitan in lakes across a 280° longitudinal and 90° latitudinal gradient. The microbiome communities were represented by a wide range of operational taxonomic units and relative abundances. Highly abundant taxa were more related and shared across most sites and did not vary with geographic distance, thus, like Microcystis , revealing no evidence for dispersal limitation. High phylogenetic relatedness, both within and across lakes, indicates that microbiome bacteria with similar functional potential were associated with all blooms. While Microcystis and the microbiome bacteria shared many genes, whole‐community metagenomic analysis revealed a suite of biochemical pathways that could be considered complementary. Our results demonstrate a high degree of similarity across global Microcystis blooms, thereby providing initial support for the hypothesized Microcystis interactome.

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

Correction to: Amyloid Precursor Protein Mediates Neuronal Protection from Rotenone Toxicity - Kathryn Cimdins; Hayley S. Waugh; Vicki Chrysostomou; M. Isabel G. Lopez Sanchez; Vanessa A. Johanssen; Mark J. Cook; Jonathan G. Crowston; Andrew F. Hill; James A. Duce; Ashley I. Bush; Ian A. Trounce (Molecular Neurobiology, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Amyloid Precursor Protein Mediates Neuronal Protection from Rotenone Toxicity - Kathryn Cimdins; Hayley S. Waugh; Vicki Chrysostomou; M. Isabel G. Lopez Sanchez; Vanessa A. Johannsen; Mark J. Cook; Jonathan G. Crowston; Andrew F. Hill; James A. Duce; Ashley I. Bush; Ian A. Trounce (Molecular Neurobiology, 2019)

Foundations and Frontiers of Ecosystem Science: Legacy of a Classic Paper (Odum 1969) - Jessica R. Corman; Scott L. Collins; Elizabeth M. Cook; Xiaoli Dong; Laureano A. Gherardi; Nancy B. Grimm; Rebecca L. Hale; Tao Lin; Jorge Ramos; Lara G. Reichmann; Osvaldo E. Sala (Ecosystems, 2019)

The state of Western Australia’s coral reefs - James P. Gilmour; Kylie L. Cook; Nicole M. Ryan; Marjetta L. Puotinen; Rebecca H. Green; George Shedrawi; Jean-Paul A. Hobbs; Damian P. Thomson; Russell C. Babcock; Joanna Buckee; Taryn Foster; Zoe T. Richards; et al. (Coral Reefs, 2019)

Tree-ring reconstructions of cool season temperature for far southeastern Australia, 1731–2007 - K. J. Allen; K. J. Anchukaitis; M. G. Grose; G. Lee; E. R. Cook; J. S. Risbey; T. J. O’Kane; D. Monselesan; A. O’Grady; S. Larsen; P. J. Baker (Climate Dynamics, 2019)

Implementation of a Systematic Tumor Screening Program for Lynch Syndrome in an Integrated Health Care Setting - Elizabeth V. Clarke; Kristin R. Muessig; Jamilyn Zepp; Jessica E. Hunter; Sapna Syngal; Louise S. Acheson; Georgia L. Wiesner; Susan K. Peterson; Kellene M. Bergen; Elizabeth Shuster; James V. Davis; Jennifer L. Schneider; et al. (Familial Cancer, 2019)

α5GABAA subunit-containing receptors and sweetened alcohol cue-induced reinstatement and active sweetened alcohol self-administration in male rats - Cassie M. Chandler; Jaren Reeves-Darby; Sherman A. Jones; J. Abigail McDonald; Guanguan Li; Md T. Rahman; James M. Cook; Donna M. Platt (Psychopharmacology, 2019)

How do climate change experiments alter plot‐scale climate? - A. K. Ettinger; I. Chuine; B. I. Cook; J. S. Dukes; A. M. Ellison; M. R. Johnston; A. M. Panetta; C. R. Rollinson; Y. Vitasse; E. M. Wolkovich (Ecology Letters, 2019)
To understand and forecast biological responses to climate change, scientists frequently use field experiments that alter temperature and precipitation. Climate manipulations can manifest in complex ways, however, challenging interpretations of biological responses. We reviewed publications to compile a database of daily plot‐scale climate data from 15 active‐warming experiments. We find that the common practices of analysing treatments as mean or categorical changes (e.g. warmed vs. unwarmed) masks important variation in treatment effects over space and time. Our synthesis showed that measured mean warming, in plots with the same target warming within a study, differed by up to 1.6 C (63% of target), on average, across six studies with blocked designs. Variation was high across sites and designs: for example, plots differed by 1.1 C (47% of target) on average, for infrared studies with feedback control ( n = 3) vs. by 2.2 C (80% of target) on average for infrared with constant wattage designs ( n = 2). Warming treatments produce non‐temperature effects as well, such as soil drying. The combination of these direct and indirect effects is complex and can have important biological consequences. With a case study of plant phenology across five experiments in our database, we show how accounting for drier soils with warming tripled the estimated sensitivity of budburst to temperature. We provide recommendations for future analyses, experimental design, and data sharing to improve our mechanistic understanding from climate change experiments, and thus their utility to accurately forecast species’ responses.

Developing a list of invasive alien species likely to threaten biodiversity and ecosystems in the European Union - Helen E. Roy; Sven Bacher; Franz Essl; Tim Adriaens; David C. Aldridge; John D. D. Bishop; Tim M. Blackburn; Etienne Branquart; Juliet Brodie; Carles Carboneras; Elizabeth J. Cottier-Cook; Gordon H. Copp; et al. (Global Change Biology, 2019)
The European Union ( EU ) has recently published its first list of invasive alien species ( IAS ) of EU concern to which current legislation must apply. The list comprises species known to pose great threats to biodiversity and needs to be maintained and updated. Horizon scanning is seen as critical to identify the most threatening potential IAS that do not yet occur in Europe to be subsequently risk assessed for future listing. Accordingly, we present a systematic consensus horizon scanning procedure to derive a ranked list of potential IAS likely to arrive, establish, spread and have an impact on biodiversity in the region over the next decade. The approach is unique in the continental scale examined, the breadth of taxonomic groups and environments considered, and the methods and data sources used. International experts were brought together to address five broad thematic groups of potential IAS . For each thematic group the experts first independently assembled lists of potential IAS not yet established in the EU but potentially threatening biodiversity if introduced. Experts were asked to score the species within their thematic group for their separate likelihoods of i) arrival, ii) establishment, iii) spread, and iv) magnitude of the potential negative impact on biodiversity within the EU . Experts then convened for a 2‐day workshop applying consensus methods to compile a ranked list of potential IAS . From an initial working list of 329 species, a list of 66 species not yet established in the EU that were considered to be very high (8 species), high (40 species) or medium (18 species) risk species was derived. Here, we present these species highlighting the potential negative impacts and the most likely biogeographic regions to be affected by these potential IAS.

Training Needs of Clinical and Research Professionals to Optimize Minority Recruitment and Retention in Cancer Clinical Trials - Soumya J. Niranjan; Raegan W. Durant; Jennifer A. Wenzel; Elise D. Cook; Mona N. Fouad; Selwyn M. Vickers; Badrinath R. Konety; Sarah B. Rutland; Zachary R. Simoni; Michelle Y. Martin (Journal of Cancer Education, 2019)

Characterization of mule deerpox virus in Florida white-tailed deer fawns expands the known host and geographic range of this emerging pathogen - Katherine A. Sayler; Kuttichantran Subramaniam; Jessica M. Jacob; Julia C. Loeb; William F. Craft; Lisa L. Farina; Nicole I. Stacy; Nissin Moussatche; Laurie Cook; John A. Lednicky; Samantha M. Wisely; Thomas B. Waltzek (Archives of Virology, 2019)

A synthesis to understand responses to capture stressors among fish discarded from commercial fisheries and options for mitigating their severity - Katrina V. Cook; Andrea J. Reid; David A. Patterson; Kendra A. Robinson; Jacqueline M. Chapman; Scott G. Hinch; Steven J. Cooke (Fish and Fisheries, 2019)
Discarding non‐target fish from commercial fisheries is controversial and has been a persistent concern for fisheries managers globally. Discard management strategies typically begin by understanding mortality rates among discarded fish, a challenging task given the dynamic, highly context‐specific nature of fisheries. An alternative is to develop our knowledge of how stressors operate by first understanding the causes of mortality that drive this context dependence. Particularly relevant to mitigation efforts is an understanding of how fish respond to the physical factors of fishing, such as the gear itself and methods of fishing and handling the gear. We provide a synthesis of how commercial fishing methods may influence discard mortality and outline means by which capture‐induced stress and injury can be mitigated for common commercial gear types, emphasizing method variants or alternatives during capture, handling, and release that could improve survival. This synthesis identifies exhaustion and injury as the most detrimental and ubiquitous stressors experienced by discarded fish, with few options for mitigating their effects. Trawls and hanging net fisheries are identified as the most harmful gears for by‐catch, characterized by high stress regardless of method variants and limited options for mitigation. Irrespective of gear type and type of stressor, minimizing durations of capture and handling and encouragement of good handling behaviour (e.g., during landing and sorting) will reduce the magnitude of stress and injury in fish, and ultimately increase survival.

Modelling glacial lake outburst flood impacts in the Bolivian Andes - Ioannis Kougkoulos; Simon J. Cook; Laura A. Edwards; Leon J. Clarke; Elias Symeonakis; Jason M. Dortch; Kathleen Nesbitt (Natural Hazards, 2018)

Delayed timing of successful spawning of an estuarine dependent fish, black bream Acanthopagrus butcheri - Gregory P. Jenkins; Julia A. Kent; Ryan J. Woodland; Fiona Warry; Stephen E. Swearer; Perran L. M. Cook (Journal of Fish Biology, 2018)
In this paper, we investigate the period of successful spawning for black bream Acanthopagrus butcheri , an obligate estuarine species in southern Australia that typically spawn in spring and early summer. However, back‐calculated spawning dates of juveniles sampled in Gippsland Lakes, Victoria from February to May 2016 indicated that spawning was concentrated over a short period in the Austral mid‐summer (January), with a second spawning in late summer and early autumn (late February–early March). Ichthyoplankton sampling in the tributary estuaries from October to early December collected substantial numbers of fish larvae, dominated by gobiids, eleotrids and retropinnids of freshwater origin, but no A. butcheri . The lack of A. butcheri larvae was consistent with the delayed successful spawning indicated by juvenile otolith data. Freshwater flows declined from late winter to summer, with consistent salinity stratification of the water column. Dissolved oxygen (DO) concentrations were generally very low below the halocline. These conditions may have delayed the upstream spawning migration of adults or may have been unsuitable for survival of eggs and newly‐hatched larvae. Longer‐term predictions for climate change in southern Victoria, including the Gippsland Lakes region, are for lower winter–spring freshwater flows, potentially benefiting the reproductive success of A. butcheri through high water‐column stratification, but only if DO concentrations are not compromised by a lack of high winter flows needed to flush low DO water from the system.

Differential Morphological and Biochemical Recovery from Chemotherapy-Induced Peripheral Neuropathy Following Paclitaxel, Ixabepilone, or Eribulin Treatment in Mouse Sciatic Nerves - B. M. Cook; K. M. Wozniak; D. A. Proctor; R. B. Bromberg; Y. Wu; B. S. Slusher; B. A. Littlefield; M. A. Jordan; L. Wilson; Stuart C. Feinstein (Neurotoxicity Research, 2018)

Genome-wide association study of primary open-angle glaucoma in continental and admixed African populations - Pieter W. M. Bonnemaijer; Adriana I. Iglesias; Girish N. Nadkarni; Anna J. Sanyiwa; Hassan G. Hassan; Colin Cook; Mark Simcoe; Kent D. Taylor; Claudia Schurmann; Gillian M. Belbin; Eimear E. Kenny; Erwin P. Bottinger; et al. (Human Genetics, 2018)

Standardized reporting of the costs of management interventions for biodiversity conservation - Gwenllian D. Iacona; William J. Sutherland; Bonnie Mappin; Vanessa M. Adams; Paul R. Armsworth; Tim Coleshaw; Carly Cook; Ian Craigie; Lynn V. Dicks; James A. Fitzsimons; Jennifer McGowan; Andrew J. Plumptre; et al. (Conservation Biology, 2018)
Effective conservation management interventions must combat threats and deliver benefits at costs that can be achieved within limited budgets. Considerable effort has focused on measuring the potential benefits of conservation interventions, but explicit quantification of the financial costs of implementation is rare. Even when costs have been quantified, haphazard and inconsistent reporting means published values are difficult to interpret. This reporting deficiency hinders progress toward a collective understanding of the financial costs of management interventions across projects and thus limits the ability to identify efficient solutions to conservation problems or attract adequate funding. We devised a standardized approach to describing financial costs reported for conservation interventions. The standards call for researchers and practitioners to describe the objective and outcome, context and methods, and scale of costed interventions, and to state which categories of costs are included and the currency and date for reported costs. These standards aim to provide enough contextual information that readers and future users can interpret the cost data appropriately. We suggest these standards be adopted by major conservation organizations, conservation science institutions, and journals so that cost reporting is comparable among studies. This would support shared learning and enhance the ability to identify and perform cost‐effective conservation.

Persistence of Hepatitis A Virus in Fresh Produce and Production Environments, and the Effect of Disinfection Procedures: A Review - N. Cook; I. Bertrand; C. Gantzer; R. M. Pinto; A. Bosch (Food and Environmental Virology, 2018)

Applying the principles of isotope analysis in plant and animal ecology to forensic science in the Americas - Lesley A. Chesson; Janet E. Barnette; Gabriel J. Bowen; J. Renée Brooks; John F. Casale; Thure E. Cerling; Craig S. Cook; Charles B. Douthitt; John D. Howa; Janet M. Hurley; Helen W. Kreuzer; Michael J. Lott; et al. (Oecologia, 2018)

Functional diversity positively affects prey suppression by invertebrate predators: a meta‐analysis - Arran Greenop; Ben A. Woodcock; Andy Wilby; Samantha M. Cook; Richard F. Pywell (Ecology, 2018)
The use of pesticides within agricultural ecosystems has led to wide concern regarding negative effects on the environment. One possible alternative is the use of predators of pest species that naturally occur within agricultural ecosystems. However, the mechanistic basis for how species can be manipulated in order to maximize pest control remains unclear. We carried out a meta‐analysis of 51 studies that manipulated predator species richness in reference to suppression of herbivore prey to determine which components of predator diversity affect pest control. Overall, functional diversity ( FD ) based on predator's habitat domain, diet breadth and hunting strategy was ranked as the most important variable. Our analysis showed that increases in FD in polycultures led to greater prey suppression compared to both the mean of the component predator species, and the most effective predator species, in monocultures. Further analysis of individual traits indicated these effects are likely to be driven by broad niche differentiation and greater resource exploitation in functionally diverse predator communities. A decoupled measure of phylogenetic diversity, whereby the overlap in variation with FD was removed, was not found to be an important driver of prey suppression. Our results suggest that increasing FD in predatory invertebrates will help maximize pest control ecosystem services in agricultural ecosystems, with the potential to increase suppression above that of the most effective predator species.

Variability of sun‐induced chlorophyll fluorescence according to stand age‐related processes in a managed loblolly pine forest - Roberto Colombo; Marco Celesti; Remo Bianchi; Petya K. E. Campbell; Sergio Cogliati; Bruce D. Cook; Lawrence A. Corp; Alexander Damm; Jean‐Christophe Domec; Luis Guanter; Tommaso Julitta; Elizabeth M. Middleton; et al. (Global Change Biology, 2018)
Leaf fluorescence can be used to track plant development and stress, and is considered the most direct measurement of photosynthetic activity available from remote sensing techniques. Red and far‐red sun‐induced chlorophyll fluorescence ( SIF ) maps were generated from high spatial resolution images collected with the HyPlant airborne spectrometer over even‐aged loblolly pine plantations in North Carolina (United States). Canopy fluorescence yield (i.e., the fluorescence flux normalized by the light absorbed) in the red and far‐red peaks was computed. This quantifies the fluorescence emission efficiencies that are more directly linked to canopy function compared to SIF radiances. Fluorescence fluxes and yields were investigated in relation to tree age to infer new insights on the potential of those measurements in better describing ecosystem processes. The results showed that red fluorescence yield varies with stand age. Young stands exhibited a nearly twofold higher red fluorescence yield than mature forest plantations, while the far‐red fluorescence yield remained constant. We interpreted this finding in a context of photosynthetic stomatal limitation in aging loblolly pine stands. Current and future satellite missions provide global datasets of SIF at coarse spatial resolution, resulting in intrapixel mixture effects, which could be a confounding factor for fluorescence signal interpretation. To mitigate this effect, we propose a surrogate of the fluorescence yield, namely the Canopy Cover Fluorescence Index ( CCFI ) that accounts for the spatial variability in canopy structure by exploiting the vegetation fractional cover. It was found that spatial aggregation tended to mask the effective relationships, while the CCFI was still able to maintain this link. This study is a first attempt in interpreting the fluorescence variability in aging forest stands and it may open new perspectives in understanding long‐term forest dynamics in response to future climatic conditions from remote sensing of SIF .

What shapes plant and animal diversity on urban golf courses? - Sabine S. Nooten; Patrick Schultheiss; Jules Wright; Catriona Macdonald; Brajesh K. Singh; James M. Cook; Sally A. Power (Urban Ecosystems, 2018)

Using biological–physical modelling for informing sea lice dispersal in Loch Linnhe, Scotland - N K G Salama; A C Dale; V V Ivanov; P F Cook; C C Pert; C M Collins; B Rabe (Journal of Fish Diseases, 2018)
Sea lice are a constraint on the sustainable growth of Scottish marine salmonid aquaculture. As part of an integrated pest management approach, farms coordinate procedures within spatial units. We present observations of copepodids being at relatively greater density than nauplii in upper waters, which informs the development of surface layer sea lice transmission modelling of Loch Linnhe, Scotland, for informing farm parasite management. A hydrodynamic model is coupled with a biological particle‐tracking model, with characteristics of plankton sea lice. Simulations are undertaken for May and October 2011–2013, forced by local wind data collected for those periods. Particles are continually released from positions representing farm locations, weighted by relative farm counts, over a 2‐week period and tracked for a further 5 days. A comparison is made between modelled relative concentrations against physical and biological surveys to provide confidence in model outputs. Connectivity between farm locations is determined in order to propose potential coordination areas. Generally, connectivity depends on flow patterns in the loch and decreases with increased farm separation. The connectivity indices are used to estimate the origins of the sea lice population composition at each site, which may influence medicinal regimens to avoid loss of efficacy.

Association between anti-tuberculosis drug resistance-conferring mutations and treatment outcomes in Myanmar - Htin Lin Aung; Thanda Tun; Wint Wint Nyunt; Yang Fong; John A. Crump; Kyi Kyi Thinn; Si Thu Aung; Gregory M. Cook (Infectious Diseases, 2018)

Expansion of landscape characterisation methods within the Hydrogeological Landscape Framework: application in the Australian Capital Territory - A. L. Cowood; C. L. Moore; M. J. Cracknell; J. Young; R. Muller; A. T. Nicholson; A. C. Wooldridge; B. R. Jenkins; W. Cook (Australian Journal of Earth Sciences, 2017)

Diversity of midwater cephalopods in the northern Gulf of Mexico: comparison of two collecting methods - H. Judkins; M. Vecchione; A. Cook; T. Sutton (Marine Biodiversity, 2017)

Influence of oceanographic conditions on abundance and distribution of post‐larval and juvenile carangid fishes in the northern Gulf of Mexico - John A. Mohan; Tracey T. Sutton; April B. Cook; Kevin M. Boswell; R. J. David Wells (Fisheries Oceanography, 2017)
Relationships between abundance of post‐larval and juvenile carangid (jacks) fishes and physical oceanographic conditions were examined in the northern Gulf of Mexico (GoM) in 2011 with high freshwater input from the Mississippi River. Generalized additive models ( GAM s) were used to explore complex relationships between carangid abundance and physical oceanographic data of sea surface temperature ( SST ), sea surface height anomaly ( SSHA ) and salinity. The five most abundant carangid species collected were: Selene setapinnis (34%); Caranx crysos (30%); Caranx hippos (10%); Chloroscombrus chrysurus (9%) and Trachurus lathami (8%). Post‐larval carangids (median standard length [ SL ] = 10 mm) were less abundant during the spring and early summer, but more abundant during the late summer and fall, suggesting summer to fall spawning for most species. Juvenile carangid (median SL = 23 mm) abundance also increased between the mid‐summer and early fall. Most species showed increased abundance at lower salinities and higher temperatures, suggesting entrainment of post‐larval fishes or feeding aggregations of juveniles at frontal convergence zones between the expansive river plume and dynamic mesoscale eddy water masses. However, responses were species‐ and life‐stage specific, which may indicate fine‐scale habitat partitioning between species. Ordination methods also revealed higher carangid abundances at lower salinities for both post‐larval and juvenile life stages, with species‐ and life‐stage specific responses to SST and SSHA , further suggesting habitat separation between species. Results indicate strong links between physical oceanographic features and carangid distributions in the dynamic northern GoM.

“The river is us; the river is in our veins”: re-defining river restoration in three Indigenous communities - Coleen A. Fox; Nicholas James Reo; Dale A. Turner; JoAnne Cook; Frank Dituri; Brett Fessell; James Jenkins; Aimee Johnson; Terina M. Rakena; Chris Riley; Ashleigh Turner; Julian Williams; et al. (Sustainability Science, 2017)

Universal screening for Lynch syndrome among patients with colorectal cancer: patient perspectives on screening and sharing results with at-risk relatives - Jessica Ezzell Hunter; Kathleen A. Arnold; Jennifer E. Cook; Jamilyn Zepp; Marian J. Gilmore; Alan F. Rope; James V. Davis; Kellene M. Bergen; Elizabeth Esterberg; Kristin R. Muessig; Susan K. Peterson; Sapna Syngal; et al. (Familial Cancer, 2017)

Genotypic diversity of Mycobacterium tuberculosis strains in Myanmar - Thanda Tun; Khin Saw Aye; Wint Wint Nyunt; John A. Crump; Chie Nakajima; Yasuhiko Suzuki; Kyi Kyi Thinn; Gregory M. Cook; Htin Lin Aung (Infectious Diseases, 2017)

Virological Quality of Irrigation Water in Leafy Green Vegetables and Berry Fruits Production Chains - P. Kokkinos; I. Kozyra; S. Lazic; K. Söderberg; P. Vasickova; M. Bouwknegt; S. Rutjes; K. Willems; R. Moloney; A. M. de Roda Husman; A. Kaupke; E. Legaki; et al. (Food and Environmental Virology, 2017)

Environmental predictors of bovine Eimeria infection in western Kenya - D. N. Makau; G. K. Gitau; G. K. Muchemi; L. F. Thomas; E. A. J. Cook; N. A. Wardrop; E. M. Fèvre; W. A. de Glanville (Tropical Animal Health and Production, 2017)

The structural history and mineralization controls of the world-class Geita Hill gold deposit, Geita Greenstone Belt, Tanzania - I. V. Sanislav; M. Brayshaw; S. L. Kolling; P. H. G. M. Dirks; Y. A. Cook; T. G. Blenkinsop (Mineralium Deposita, 2017)

A longitudinal study of patients with cirrhosis treated with L-ornithine L-aspartate, examined with magnetization transfer, diffusion-weighted imaging and magnetic resonance spectroscopy - Vijay P. B. Grover; Mark J. W. McPhail; Marzena Wylezinska-Arridge; Mary M. E. Crossey; Julie A. Fitzpatrick; Louise Southern; Brian K. Saxby; Nicola A. Cook; I. Jane Cox; Adam D. Waldman; Novraj S. Dhanjal; Aluel Bak-Bol; et al. (Metabolic Brain Disease, 2017)

Qualifying and quantifying minimal hepatic encephalopathy - Marsha Y. Morgan; Piero Amodio; Nicola A. Cook; Clive D. Jackson; Gerald Kircheis; Mette M. Lauridsen; Sara Montagnese; Sami Schiff; Karin Weissenborn (Metabolic Brain Disease, 2016)

Metabolome‐mediated biocryomorphic evolution promotes carbon fixation in G reenlandic cryoconite holes - Joseph M. Cook; Arwyn Edwards; Mark Bulling; Luis A. J. Mur; Sophie Cook; Jarishma K. Gokul; Karen A. Cameron; Michael Sweet; Tristram D. L. Irvine‐Fynn (Environmental Microbiology, 2016)
Summary Microbial photoautotrophs on glaciers engineer the formation of granular microbial‐mineral aggregates termed cryoconite which accelerate ice melt, creating quasi‐cylindrical pits called ‘cryoconite holes’. These act as biogeochemical reactors on the ice surface and provide habitats for remarkably active and diverse microbiota. Evolution of cryoconite holes towards an equilibrium depth is well known, yet interactions between microbial activity and hole morphology are currently weakly addressed. Here, we experimentally perturbed the depths and diameters of cryoconite holes on the Greenland Ice Sheet. Cryoconite holes responded by sensitively adjusting their shapes in three dimensions (‘biocryomorphic evolution’) thus maintaining favourable conditions for net autotrophy at the hole floors. Non‐targeted metabolomics reveals concomitant shifts in cyclic AMP and fucose metabolism consistent with phototaxis and extracellular polymer synthesis indicating metabolomic‐level granular changes in response to perturbation. We present a conceptual model explaining this process and suggest that it results in remarkably robust net autotrophy on the Greenland Ice Sheet. We also describe observations of cryoconite migrating away from shade, implying a degree of self‐regulation of carbon budgets over mesoscales. Since cryoconite is a microbe‐mineral aggregate, it appears that microbial processes themselves form and maintain stable autotrophic habitats on the surface of the Greenland ice sheet.

Codivergence of the primary bacterial endosymbiont of psyllids versus host switches and replacement of their secondary bacterial endosymbionts - Aidan A. G. Hall; Jennifer L. Morrow; Caroline Fromont; Martin J. Steinbauer; Gary S. Taylor; Scott N. Johnson; James M. Cook; Markus Riegler (Environmental Microbiology, 2016)
Summary Coevolution between insects and bacterial endosymbionts contributes to the success of many insect lineages. For the first time, we tested for phylogenetic codivergence across multiple taxonomic scales, from within genera to superfamily between 36 psyllid species of seven recognised families (Hemiptera: Psylloidea), their exclusive primary endosymbiont Carsonella and more diverse secondary endosymbionts (S‐endosymbionts). Within Aphalaridae, we found that Carsonella and S‐endosymbionts were fixed in one Glycaspis and 12 Cardiaspina populations. The dominant S‐endosymbiont was Arsenophonus , while Sodalis was detected in one Cardiaspina species. We demonstrated vertical transmission for Carsonella and Arsenophonus in three Cardiaspina species. We found strong support for strict cospeciation and validated the informative content of Carsonella as extended host genome for inference of psyllid relationships. However, S‐endosymbiont and host phylogenies were incongruent, and displayed signs of host switching and endosymbiont replacement. The high incidence of Arsenophonus in psyllids and other plant sap‐feeding Hemiptera may be due to repeated host switching within this group. In two psyllid lineages, Arsenophonus and Sodalis genes exhibited accelerated evolutionary rates and AT‐biases characteristic of long‐term host associations. Together with strict vertical transmission and 100% prevalence within host populations, our results suggest an obligate, and not facultative, symbiosis between psyllids and some S‐endosymbionts.

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

A trans‐Atlantic examination of haddock Melanogrammus aeglefinus food habits - J. C. Tam; J. S. Link; S. I. Large; B. Bogstad; A. Bundy; A. M. Cook; G. E. Dingsør; A. V. Dolgov; D. Howell; A. Kempf; J. K. Pinnegar; A. Rindorf; et al. (Journal of Fish Biology, 2016)
The food habits of Melanogrammus aeglefinus were explored and contrasted across multiple north‐eastern and north‐western Atlantic Ocean ecosystems, using databases that span multiple decades. The results show that among all ecosystems, echinoderms are a consistent part of M. aeglefinus diet, but patterns emerge regarding where and when M. aeglefinus primarily eat fishes v . echinoderms. Melanogrammus aeglefinus does not regularly exhibit the increase in piscivory with ontogeny that other gadoids often show, and in several ecosystems there is a lower occurrence of piscivory. There is an apparent inverse relationship between the consumption of fishes and echinoderms in M. aeglefinus over time, where certain years show high levels of one prey item and low levels of the other. This apparent binary choice can be viewed as part of a gradient of prey options, contingent upon a suite of factors external to M. aeglefinus dynamics. The energetic consequences of this prey choice are discussed, noting that in some instances it may not be a choice at all.

Erratum to: Sex-specific macronutrient foraging strategies in a highly successful marine predator: the Australasian gannet - Gabriel E. Machovsky-Capuska; Alistair M. Senior; Emily C. Benn; Alice H. Tait; Rob Schuckard; Karen A. Stockin; Willie Cook; Mike Ogle; Katherine Barna; David Melville; Belinda Wright; Cameron Purvin; et al. (Marine Biology, 2016)

Sex-specific macronutrient foraging strategies in a highly successful marine predator: the Australasian gannet - Gabriel E. Machovsky-Capuska; Alistair M. Senior; Emily C. Benn; Alice H. Tait; Rob Schuckard; Karen A. Stockin; Willie Cook; Mike Ogle; Katherine Barna; David Melville; Belinda Wright; Cameron Purvin; et al. (Marine Biology, 2016)

Post-traumatic stress is associated with verbal learning, memory, and psychomotor speed in HIV-infected and HIV-uninfected women - Leah H. Rubin; Maria Pyra; Judith A. Cook; Kathleen M. Weber; Mardge H. Cohen; Eileen Martin; Victor Valcour; Joel Milam; Kathryn Anastos; Mary A. Young; Christine Alden; Deborah R. Gustafson; et al. (Journal of NeuroVirology, 2016)

Use of an allostatic neurotechnology by adolescents with postural orthostatic tachycardia syndrome (POTS) is associated with improvements in heart rate variability and changes in temporal lobe electrical activity - John E. Fortunato; Catherine L. Tegeler; Lee Gerdes; Sung W. Lee; Nicholas M. Pajewski; Meghan E. Franco; Jared F. Cook; Hossam A. Shaltout; Charles H. Tegeler (Experimental Brain Research, 2016)

Systems genetics of intravenous cocaine self-administration in the BXD recombinant inbred mouse panel - Price E. Dickson; Mellessa M. Miller; Michele A. Calton; Jason A. Bubier; Melloni N. Cook; Daniel Goldowitz; Elissa J. Chesler; Guy Mittleman (Psychopharmacology, 2016)

Effects of Paclitaxel and Eribulin in Mouse Sciatic Nerve: A Microtubule-Based Rationale for the Differential Induction of Chemotherapy-Induced Peripheral Neuropathy - Sarah J. Benbow; Brett M. Cook; Jack Reifert; Krystyna M. Wozniak; Barbara S. Slusher; Bruce A. Littlefield; Leslie Wilson; Mary Ann Jordan; Stuart C. Feinstein (Neurotoxicity Research, 2016)

Antidepressant treatment history and drug-placebo separation in a placebo-controlled trial in major depressive disorder - Aimee M. Hunter; Ian A. Cook; Molly Tartter; Simi K. Sharma; Gregory D. Disse; Andrew F. Leuchter (Psychopharmacology, 2015)

Cardiorespiratory fitness is associated with brain structure, cognition, and mood in a middle-aged cohort at risk for Alzheimer’s disease - Elizabeth A. Boots; Stephanie A. Schultz; Jennifer M. Oh; Jordan Larson; Dorothy Edwards; Dane Cook; Rebecca L. Koscik; Maritza N. Dowling; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; et al. (Brain Imaging and Behavior, 2015)

The association of perceived stress and verbal memory is greater in HIV-infected versus HIV-uninfected women - Leah H. Rubin; Judith A. Cook; Kathleen M. Weber; Mardge H. Cohen; Eileen Martin; Victor Valcour; Joel Milam; Kathryn Anastos; Mary A. Young; Christine Alden; Deborah R. Gustafson; Pauline M. Maki (Journal of NeuroVirology, 2015)

The effects of foundation species on community assembly: a global study on alpine cushion plant communities - Zaal Kikvidze; Robin W. Brooker; Bradley J. Butterfield; Ragan M. Callaway; Lohengrin A. Cavieres; Bradley J. Cook; Christopher J. Lortie; Richard Michalet; Francisco I. Pugnaire; Sa Xiao; Fabien Anthelme; Robert G. Björk; et al. (Ecology, 2015)
Foundation species can change plant community structure by modulating important ecological processes such as community assembly, yet this topic is poorly understood. In alpine systems, cushion plants commonly act as foundation species by ameliorating local conditions. Here, we analyze diversity patterns of species' assembly within cushions and in adjacent surrounding open substrates (83 sites across five continents) calculating floristic dissimilarity between replicate plots, and using linear models to analyze relationships between microhabitats and species diversity. Floristic dissimilarity did not change across biogeographic regions, but was consistently lower in the cushions than in the open microhabitat. Cushion plants appear to enable recruitment of many relatively stress‐intolerant species that otherwise would not establish in these communities, yet the niche space constructed by cushion plants supports a more homogeneous composition of species than the niche space beyond the cushion's influence. As a result, cushion plants support higher α‐diversity and a larger species pool, but harbor assemblies with lower β‐diversity than open microhabitats. We conclude that habitats with and without dominant foundation species can strongly differ in the processes that drive species recruitment, and thus the relationship between local and regional species diversity.

Evidence of climate‐driven ecosystem reorganization in the Gulf of Mexico - Mandy Karnauskas; Michael J. Schirripa; J. K. Craig; Geoffrey S. Cook; Christopher R. Kelble; Juan J. Agar; Bryan A. Black; David B. Enfield; David Lindo‐Atichati; Barbara A. Muhling; Kevin M. Purcell; Paul M. Richards; et al. (Global Change Biology, 2015)
The Gulf of Mexico is one of the most ecologically and economically valuable marine ecosystems in the world and is affected by a variety of natural and anthropogenic phenomena including climate, hurricanes, coastal development, agricultural runoff, oil spills, and fishing. These complex and interacting stressors, together with the highly dynamic nature of this ecosystem, present challenges for the effective management of its resources. We analyze a compilation of over 100 indicators representing physical, biological, and economic aspects of the Gulf of Mexico and find that an ecosystem‐wide reorganization occurred in the mid‐1990s. Further analysis of fishery landings composition data indicates a major shift in the late 1970s coincident with the advent of US national fisheries management policy, as well as significant shifts in the mid‐1960s and the mid‐1990s. These latter shifts are aligned temporally with changes in a major climate mode in the Atlantic Ocean: the Atlantic Multidecadal Oscillation ( AMO ). We provide an explanation for how the AMO may drive physical changes in the Gulf of Mexico, thus altering higher‐level ecosystem dynamics. The hypotheses presented here should provide focus for further targeted studies, particularly in regard to whether and how management should adjust to different climate regimes or states of nature. Our study highlights the challenges in understanding the effects of climatic drivers against a background of multiple anthropogenic pressures, particularly in a system where these forces interact in complex and nonlinear ways.

Sex differences in ventricular–vascular coupling following endurance training - A. D. Lane; H. Yan; S. M. Ranadive; R. M. Kappus; P. Sun; M. D. Cook; I. Harvey; J. Woods; K. Wilund; B. Fernhall (European Journal of Applied Physiology, 2014)

Horizon scanning for invasive alien species with the potential to threaten biodiversity in Great Britain - Helen E. Roy; Jodey Peyton; David C. Aldridge; Tristan Bantock; Tim M. Blackburn; Robert Britton; Paul Clark; Elizabeth Cook; Katharina Dehnen‐Schmutz; Trevor Dines; Michael Dobson; François Edwards; et al. (Global Change Biology, 2014)
Invasive alien species ( IAS ) are considered one of the greatest threats to biodiversity, particularly through their interactions with other drivers of change. Horizon scanning, the systematic examination of future potential threats and opportunities, leading to prioritization of IAS threats is seen as an essential component of IAS management. Our aim was to consider IAS that were likely to impact on native biodiversity but were not yet established in the wild in Great Britain. To achieve this, we developed an approach which coupled consensus methods (which have previously been used for collaboratively identifying priorities in other contexts) with rapid risk assessment. The process involved two distinct phases: Preliminary consultation with experts within five groups (plants, terrestrial invertebrates, freshwater invertebrates, vertebrates and marine species) to derive ranked lists of potential IAS. Consensus‐building across expert groups to compile and rank the entire list of potential IAS. Five hundred and ninety‐one species not native to Great Britain were considered. Ninety‐three of these species were agreed to constitute at least a medium risk (based on score and consensus) with respect to them arriving, establishing and posing a threat to native biodiversity. The quagga mussel, Dreissena rostriformis bugensis , received maximum scores for risk of arrival, establishment and impact; following discussions the unanimous consensus was to rank it in the top position. A further 29 species were considered to constitute a high risk and were grouped according to their ranked risk. The remaining 63 species were considered as medium risk, and included in an unranked long list. The information collated through this novel extension of the consensus method for horizon scanning provides evidence for underpinning and prioritizing management both for the species and, perhaps more importantly, their pathways of arrival. Although our study focused on Great Britain, we suggest that the methods adopted are applicable globally.

Reduction of circulating and selective limbic brain levels of (3α,5α)-3-hydroxy-pregnan-20-one (3α,5α-THP) following forced swim stress in C57BL/6J mice - Antoniette M. Maldonado-Devincci; Matthew C. Beattie; Danielle H. Morrow; Raechel E. McKinley; Jason B. Cook; Todd K. O’Buckley; A. Leslie Morrow (Psychopharmacology, 2014)

Pore‐water exchange driven by tidal pumping causes alkalinity export in two intertidal inlets - Peter A. Faber; Victor Evrard; Ryan J. Woodland; Ian C. Cartwright; Perran L. M. Cook (Limnology and Oceanography, 2014)
Carbon (C) and alkalinity export from two adjacent intertidal inlets with different terrestrial inputs was investigated. One inlet receives a small creek from an agriculturally dominated catchment, leading to the input of terrestrially sourced material, whereas the other is relatively isolated from terrestrial inputs. Using time‐series measurements, we calculated the total advective exchange of dissolved organic C (DOC; 0–25 mmol m ‒2 d ‒1 ), dissolved inorganic C (DIC; 130–450 mmol m ‒2 d ‒1 ), total alkalinity (TA; 46–310 mmol m ‒ d ‒1 ), and the nutrients nitrate (1.0–1.1 mmol m ‒2 d ‒1 ), ammonia (0.0043–0.10 mmol m ‒2 d ‒1 ), and phosphorus (0.016–0.25 mmol m ‒2 d ‒1 ). Radon‐222 ( 222 Rn) data indicated that pore‐water exchange played an important part in controlling C export from the sediment as an advective flux. The residence time of pore water within both inlets was ~ 6.6–7.4 h, indicating that pore‐water exchange is driven by tidal pumping. The inlet with the greater amount of terrestrial inputs exported much more TA (310 vs. 46 mmol m ‒2 d ‒1 ), suggesting that the extent of land‐to‐sea connectivity influences how C is exported. We hypothesize that this is due to the increased input of iron (Fe) from terrestrial sources, which fosters net TA production through the burial of reduced sulfur species as Fe sulfides. A simple mass balance showed that the TA fluxes observed over 24 h were higher than could be sustained continuously with Fe input from the catchment (0.49 mmol Fe m ‒2 d ‒1 ), meaning that the observed TA fluxes could not be sustained on long timescales. It is most likely that there are periods of net reduction and net oxidation in response to wave action and calm conditions, highlighting the importance of long‐term monitoring over different seasons and weather patterns to obtain representative budgets.

Hydroacoustic tracking of the endangered Atlantic whitefish (Coregonus huntsmani); comparative analysis from wild and hatchery reared populations - A. M. Cook; R. G. Bradford; P. Bentzen (Environmental Biology of Fishes, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Turning passive detection systems into field experiments: an application using wetland fishes and enclosures to track fine-scale movement and habitat choice - J. S. Rehage; R. E. Boucek; E. A. Cline; M. I. Cook; R. M. Kobza; A. K. Saha (acta ethologica, 2014)

Characterising the distribution of near-shore submarine groundwater discharge along a coastline using 222 Rn and electrical conductivity - M. A. Short; S. Lamontagne; P. G. Cook; R. Cranswick (Australian Journal of Earth Sciences, 2014)

The relationship between glycine transporter 1 occupancy and the effects of the glycine transporter 1 inhibitor RG1678 or ORG25935 on object retrieval performance in scopolamine impaired rhesus monkey - Donnie Eddins; Terence G. Hamill; Vanita Puri; Christopher E. Cannon; Jeffrey A. Vivian; Sandra M. Sanabria-Bohórquez; Jacquelynn J. Cook; John A. Morrow; Fiona Thomson; Jason M. Uslaner (Psychopharmacology, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2014)
HIV-associated neurocognitive disorder (HAND), characterized by a wide spectrum of behavioral, cognitive, and motor dysfunctions, continues to affect approximately 50 % of HIV(+) patients despite the success of combination antiretroviral drug therapy (cART) in the periphery. Of note, potential toxicity of antiretroviral drugs in the central nervous system (CNS) remains remarkably underexplored and may contribute to the persistence of HAND in the cART era. Previous studies have shown antiretrovirals (ARVs) to be neurotoxic in the peripheral nervous system in vivo and in peripheral neurons in vitro. Alterations in lipid and protein metabolism, mitochondrial damage, and oxidative stress all play a role in peripheral ARV neurotoxicity. We hypothesized that ARVs also induce cellular stresses in the CNS, ultimately leading to neuronal damage and contributing to the changing clinical and pathological picture seen in HIV-positive patients in the cART era. In this report, we show that ARVs are neurotoxic in the CNS in both pigtail macaques and rats in vivo. Furthermore, in vitro, ARVs lead to accumulation of reactive oxygen species (ROS), and ultimately induction of neuronal damage and death. Whereas ARVs alone caused some activation of the endogenous antioxidant response in vitro, augmentation of this response by a fumaric acid ester, monomethyl fumarate (MMF), blocked ARV-induced ROS generation, and neuronal damage/death. These findings implicate oxidative stress as a contributor to the underlying mechanisms of ARV-induced neurotoxicity and will provide an access point for adjunctive therapies to complement ARV therapy and reduce neurotoxicity in this patient population.

Facilitative plant interactions and climate simultaneously drive alpine plant diversity - Lohengrin A. Cavieres; Rob W. Brooker; Bradley J. Butterfield; Bradley J. Cook; Zaal Kikvidze; Christopher J. Lortie; Richard Michalet; Francisco I. Pugnaire; Christian Schöb; Sa Xiao; Fabien Anthelme; Robert G. Björk; et al. (Ecology Letters, 2014)
Interactions among species determine local‐scale diversity, but local interactions are thought to have minor effects at larger scales. However, quantitative comparisons of the importance of biotic interactions relative to other drivers are rarely made at larger scales. Using a data set spanning 78 sites and five continents, we assessed the relative importance of biotic interactions and climate in determining plant diversity in alpine ecosystems dominated by nurse‐plant cushion species. Climate variables related with water balance showed the highest correlation with richness at the global scale. Strikingly, although the effect of cushion species on diversity was lower than that of climate, its contribution was still substantial. In particular, cushion species enhanced species richness more in systems with inherently impoverished local diversity. Nurse species appear to act as a ‘safety net’ sustaining diversity under harsh conditions, demonstrating that climate and species interactions should be integrated when predicting future biodiversity effects of climate change.

Convergent structure of multitrophic communities over three continents - Simon T. Segar; Rodrigo A. S. Pereira; Steve G. Compton; James M. Cook (Ecology Letters, 2013)
Astract Ecological theory predicts that communities using the same resources should have similar structure, but evolutionary constraints on colonisation and niche shifts may hamper such convergence. Multitrophic communities of wasps exploiting fig fruits, which first evolved about 75 MYA , do not show long‐term ‘inheritance’ of taxonomic (lineage) composition or species diversity. However, communities on three continents have converged ecologically in the presence and relative abundance of five insect guilds that we define. Some taxa fill the same niches in each community (phylogenetic niche conservatism). However, we show that overall convergence in ecological community structure depends also on a combination of niche shifts by resident lineages and local colonisations of figs by other insect lineages. Our study explores new ground, and develops new heuristic tools, in combining ecology and phylogeny to address patterns in the complex multitrophic communities of insect on plants, which comprise a large part of terrestrial biodiversity.

Upper thermal tolerances of key taxonomic groups of stream invertebrates - Barbara A. Stewart; Paul G. Close; Peter A. Cook; Peter M. Davies (Hydrobiologia, 2013)

GidA Expression in Salmonella is Modulated Under Certain Environmental Conditions - Jaclyn M. Rehl; Daniel C. Shippy; Nicholas M. Eakley; Megan D. Brevik; Jordan M. Sand; Mark E. Cook; Amin A. Fadl (Current Microbiology, 2013)

Reliability of individual and pooled test procedures for detecting the pathogenic agent for clinical infectious salmon anaemia - M Hall; I S Wallace; L A Munro; E S Munro; R McIntosh; P Cook; C E T Allan; A G Murray (Journal of Fish Diseases, 2013)

Development and characterization of 21 polymorphic microsatellite markers for the barren-ground shrew, Sorex ugyunak (Mammalia: Sorcidae), through next-generation sequencing, and cross-species amplification in the masked shrew, S. cinereus - S. A. Sonsthagen; G. K. Sage; M. Fowler; A. G. Hope; J. A. Cook; S. L. Talbot (Conservation Genetics Resources, 2013)

Red oilseed rape? The potential for manipulation of petal colour in control strategies for the pollen beetle (Meligethes aeneus) - Samantha M. Cook; Matthew P. Skellern; Thomas F. Döring; John A. Pickett (Arthropod-Plant Interactions, 2013)

Role of gamma-aminobutyric acid type A (GABAA) receptor subtypes in acute benzodiazepine physical dependence-like effects: evidence from squirrel monkeys responding under a schedule of food presentation - Bradford D. Fischer; Laura P. Teixeira; Michael L. van Linn; Ojas A. Namjoshi; James M. Cook; James K. Rowlett (Psychopharmacology, 2013)

Alpine cushion plants inhibit the loss of phylogenetic diversity in severe environments - B. J. Butterfield; L. A. Cavieres; R. M. Callaway; B. J. Cook; Z. Kikvidze; C. J. Lortie; R. Michalet; F. I. Pugnaire; C. Schöb; S. Xiao; B. Zaitchek; F. Anthelme; et al. (Ecology Letters, 2013)
Biotic interactions can shape phylogenetic community structure (PCS). However, we do not know how the asymmetric effects of foundation species on communities extend to effects on PCS. We assessed PCS of alpine plant communities around the world, both within cushion plant foundation species and adjacent open ground, and compared the effects of foundation species and climate on alpha (within‐microsite), beta (between open and cushion) and gamma (open and cushion combined) PCS. In the open, alpha PCS shifted from highly related to distantly related with increasing potential productivity. However, we found no relationship between gamma PCS and climate, due to divergence in phylogenetic composition between cushion and open sub‐communities in severe environments, as demonstrated by increasing phylo‐beta diversity. Thus, foundation species functioned as micro‐refugia by facilitating less stress‐tolerant lineages in severe environments, erasing a global productivity – phylogenetic diversity relationship that would go undetected without accounting for this important biotic interaction.

Harmonised Investigation of the Occurrence of Human Enteric Viruses in the Leafy Green Vegetable Supply Chain in Three European Countries - P. Kokkinos; I. Kozyra; S. Lazic; M. Bouwknegt; S. Rutjes; K. Willems; R. Moloney; A. M. de Roda Husman; A. Kaupke; E. Legaki; M. D’Agostino; N. Cook; et al. (Food and Environmental Virology, 2012)

Summary Workshop Report: Facilitating Oral Product Development and Reducing Regulatory Burden Through Novel Approaches to Assess Bioavailability/Bioequivalence - James E. Polli; Jack A. Cook; Barbara M. Davit; Paul A. Dickinson; Domenick Argenti; Nancy Barbour; Alfredo García-Arieta; Jean-Marie Geoffroy; Kerry Hartauer; Shoufeng Li; Amitava Mitra; Francis X. Muller; et al. (The AAPS Journal, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Ubiquitous Brms1 expression is critical for mammary carcinoma metastasis suppression via promotion of apoptosis - Leah M. Cook; Xuemei Cao; Alexander E. Dowell; Michael T. Debies; Mick D. Edmonds; Benjamin H. Beck; Robert A. Kesterson; Renee A. Desmond; Andra R. Frost; Douglas R. Hurst; Danny R. Welch (Clinical & Experimental Metastasis, 2012)

Thoracic Artificial Lung Impedance Studies Using Computational Fluid Dynamics and In Vitro Models - Rebecca E. Schewe; Khalil M. Khanafer; Ryan A. Orizondo; Keith E. Cook (Annals of Biomedical Engineering, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Tobacco withdrawal components and their relations with cessation success - Megan E. Piper; Tanya R. Schlam; Jessica W. Cook; Megan A. Sheffer; Stevens S. Smith; Wei-Yin Loh; Daniel M. Bolt; Su-Young Kim; Jesse T. Kaye; Kathryn R. Hefner; Timothy B. Baker (Psychopharmacology, 2011)

Development and use of genic molecular markers (GMMs) for construction of a transcript map of chickpea (Cicer arietinum L.) - Neha Gujaria; Ashish Kumar; Preeti Dauthal; Anuja Dubey; Pavana Hiremath; A. Bhanu Prakash; Andrew Farmer; Mangla Bhide; Trushar Shah; Pooran M. Gaur; Hari D. Upadhyaya; Sabhyata Bhatia; et al. (Theoretical and Applied Genetics, 2011)

Broad‐scale latitudinal patterns of genetic diversity among native European and introduced house sparrow ( Passer domesticus ) populations - A. W. SCHREY; M. GRISPO; M. AWAD; M. B. COOK; E. D. McCOY; H. R. MUSHINSKY; T. ALBAYRAK; S. BENSCH; T. BURKE; L. K. BUTLER; R. DOR; H. B. FOKIDIS; et al. (Molecular Ecology, 2011)
Introduced species offer unique opportunities to study evolution in new environments, and some provide opportunities for understanding the mechanisms underlying macroecological patterns. We sought to determine how introduction history impacted genetic diversity and differentiation of the house sparrow ( Passer domesticus ), one of the most broadly distributed bird species. We screened eight microsatellite loci in 316 individuals from 16 locations in the native and introduced ranges. Significant population structure occurred between native than introduced house sparrows. Introduced house sparrows were distinguished into one North American group and a highly differentiated Kenyan group. Genetic differentiation estimates identified a high magnitude of differentiation between Kenya and all other populations, but demonstrated that European and North American samples were differentiated too. Our results support previous claims that introduced North American populations likely had few source populations, and indicate house sparrows established populations after introduction. Genetic diversity also differed among native, introduced North American, and Kenyan populations with Kenyan birds being least diverse. In some cases, house sparrow populations appeared to maintain or recover genetic diversity relatively rapidly after range expansion (

Factors limiting the health of semi-scavenging ducks in Bangladesh - M. A. Hoque; L. F. Skerratt; A. J. C. Cook; S. A. Khan; D. Grace; M. R. Alam; A. Vidal-Diez; N. C. Debnath (Tropical Animal Health and Production, 2011)

Population structure and linkage disequilibrium in oat (Avena sativa L.): implications for genome-wide association studies - M. A. Newell; D. Cook; N. A. Tinker; J.-L. Jannink (Theoretical and Applied Genetics, 2011)

You are what you eat, whenever or wherever you eat it: an integrative analysis of fish food habits in Canadian and U.S.A. waters - A. Bundy; J. S. Link; B. E. Smith; A. M. Cook (Journal of Fish Biology, 2011)
The degree to which fish diet differs by season and area, particularly over broad scales, was examined for the first time in temperate, contiguous north‐west Atlantic Ocean waters by comparing food habit data for 10 species of fishes collected concurrently during the spring and autumn surveys in the U.S.A. (Gulf of Maine proper and Georges Bank) and in the summer survey in Canada (western Scotian Shelf and Bay of Fundy). For most species, there was a general concurrence among the three seasons and four areas: summer diets had the same dominant prey items as spring and autumn diets. Although a suite of multivariate analyses did elucidate some differences in specific proportions of the diet for these species across seasons and areas, the main prey did not substantially change for most of these species. These results suggest that there are (1) minimal differences in diet across season for these species at these taxonomic resolutions, (2) there are minimal differences in diet geographically for these species and (3) differences across species, as expected, are important. Many fisheries ecosystem and multispecies models are dependent on food habit data, where resolving seasonal and spatial differences in diet remains an important consideration; however, the present work implies that amalgamated estimates of diet from seasonal surveys may be a reasonable approach when no finer seasonal resolution exists, as long as due diligence is exercised.

Case–control study of lifetime total physical activity and endometrial cancer risk - Christine M. Friedenreich; Linda S. Cook; Anthony M. Magliocco; Máire A. Duggan; Kerry S. Courneya (Cancer Causes & Control, 2010)

Microcyclic conidiogenesis in powdery mildews and its association with intracellular parasitism by Ampelomyces - Levente Kiss; Alexandra Pintye; Györgyi Zséli; Tünde Jankovics; Orsolya Szentiványi; Yaser M. Hafez; Roger T. A. Cook (European Journal of Plant Pathology, 2010)

The petrogenesis of sodic island arc magmas at Savo volcano, Solomon Islands - D. J. Smith; M. G. Petterson; A. D. Saunders; I. L. Millar; G. R. T. Jenkin; T. Toba; J. Naden; J. M. Cook (Contributions to Mineralogy and Petrology, 2009)

Glutamatergic and GABAergic modulations of ultrasonic vocalizations during maternal separation distress in mouse pups - Aki Takahashi; Jasmine J. Yap; Dawnya Zitzman Bohager; Sara Faccidomo; Terry Clayton; James M. Cook; Klaus A. Miczek (Psychopharmacology, 2009)

Phylogenetic analysis of actinobacterial populations associated with Antarctic Dry Valley mineral soils - Olubukola O. Babalola; Bronwyn M. Kirby; Marilize Le Roes‐Hill; Andrew E. Cook; S. Craig Cary; Stephanie G. Burton; Don A. Cowan (Environmental Microbiology, 2009)
Summary Despite the apparent severity of the environmental conditions in the McMurdo Dry Valleys, Eastern Antarctica, recent phylogenetic studies conducted on mineral soil samples have revealed the presence of a wide diversity of microorganisms, with actinobacteria representing one of the largest phylotypic groups. Previous metagenomic studies have shown that the majority of Antarctic actinobacterial populations are classified as ‘uncultured’. In this study, we assessed the diversity of actinobacteria in Antarctic cold desert soils by complementing traditional culture‐based techniques with a metagenomic study. Phylogenetic analysis of clones generated with actinobacterium‐ and streptomycete‐specific PCR primers revealed that the majority of the phylotypes were most closely related to uncultured Pseudonocardia and Nocardioides species. Phylotypes most closely related to a number of rarer actinobacteria genera, including Geodermatophilus , Modestobacter and Sporichthya , were also identified. While complementary culture‐dependent studies isolated a number of Nocardia and Pseudonocardia species, the majority of the cultured isolates (> 80%) were S treptomyces species – although phylotypes affiliated to the genus Streptomyces were detected at a low frequency in the metagenomic study. This study confirms that Antarctic Dry Valley desert soil harbours highly diverse actinobacterial communities and suggests that many of the phylotypes identified may represent novel, uncultured species.

Cryptic seedling herbivory by nocturnal introduced generalists impacts survival, performance of native and exotic plants - Sharon Y. Strauss; Maureen L. Stanton; Nancy C. Emery; Carrie A. Bradley; Alexandra Carleton; Dylan R. Dittrich-Reed; Olivia A. Ervin; Levi N. Gray; Andrew M. Hamilton; Jennifer Harrington Rogge; Skye D. Harper; Kimberley Cook Law; et al. (Ecology, 2009)
Although much of the theory on the success of invasive species has been geared at escape from specialist enemies, the impact of introduced generalist invertebrate herbivores on both native and introduced plant species has been underappreciated. The role of nocturnal invertebrate herbivores in structuring plant communities has been examined extensively in Europe, but less so in North America. Many nocturnal generalists (slugs, snails, and earwigs) have been introduced to North America, and 96% of herbivores found during a night census at our California Central Valley site were introduced generalists. We explored the role of these herbivores in the distribution, survivorship, and growth of 12 native and introduced plant species from six families. We predicted that introduced species sharing an evolutionary history with these generalists might be less vulnerable than native plant species. We quantified plant and herbivore abundances within our heterogeneous site and also established herbivore removal experiments in 160 plots spanning the gamut of microhabitats. As 18 collaborators, we checked 2000 seedling sites every day for three weeks to assess nocturnal seedling predation. Laboratory feeding trials allowed us to quantify the palatability of plant species to the two dominant nocturnal herbivores at the site (slugs and earwigs) and allowed us to account for herbivore microhabitat preferences when analyzing attack rates on seedlings. The relationship between local slug abundance and percent cover of five common plant taxa at the field site was significantly negatively associated with the mean palatability of these taxa to slugs in laboratory trials. Moreover, seedling mortality of 12 species in open‐field plots was positively correlated with mean palatability of these taxa to both slugs and earwigs in laboratory trials. Counter to expectations, seedlings of native species were neither more vulnerable nor more palatable to nocturnal generalists than those of introduced species. Growth comparison of plants within and outside herbivore exclosures also revealed no differences between native and introduced plant species, despite large impacts of herbivores on growth. Cryptic nocturnal predation on seedlings was common and had large effects on plant establishment at our site. Without intensive monitoring, such predation could easily be misconstrued as poor seedling emergence.

Brain Electrical Source Differences between Depressed Subjects and Healthy Controls - Alexander S. Korb; Ian A. Cook; Aimee M. Hunter; Andrew F. Leuchter (Brain Topography, 2008)

Therapeutic frontiers: preventing and treating infectious diseases by inhibiting bacterial quorum sensing - C. A. Martin; A. D. Hoven; A. M. Cook (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Summary Workshop Report: Bioequivalence, Biopharmaceutics Classification System, and Beyond - James E. Polli; Bertil S. I. Abrahamsson; Lawrence X. Yu; Gordon L. Amidon; John M. Baldoni; Jack A. Cook; Paul Fackler; Kerry Hartauer; Gordon Johnston; Steve L. Krill; Robert A. Lipper; Waseem A. Malick; et al. (The AAPS Journal, 2008)

Marine Metapopulations - Celeste Benham; Alison M. Cawood; Geoffrey S. Cook; Ange Darnell; Peter C. Davison; Miriam C. Goldstein; Ayana Elizabeth Johnson; Talina Konotchick; Elisa M. Maldonado; Alexis L. Pasulka; Jennifer C. Prairie; Serena M. Moseman; et al. (Marine Ecology, 2008)

Genetic variants in the 8q24 locus and risk of testicular germ cell tumors - Michael B. Cook; Barry I. Graubard; Sabah M. Quraishi; Meredith Yeager; Stephen J. Chanock; Andrew Crenshaw; Ralph L. Erickson; Mark V. Rubertone; Gilles Thomas; Katherine A. McGlynn (Human Genetics, 2008)

Andropogon gayanus (Gamba Grass) Invasion Increases Fire-mediated Nitrogen Losses in the Tropical Savannas of Northern Australia - N. A. Rossiter-Rachor; S. A. Setterfield; M. M. Douglas; L. B. Hutley; G. D. Cook (Ecosystems, 2008)

Impact of canal development on intertidal microalgal productivity: Comparative assessment of Patterson Lakes and Ralphs Bay, South East Australia - S. S. Cook; J. L. Roberts; G. M. Hallegraeff; A. McMinn (Journal of Coastal Conservation, 2007)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Tellurides from Sunrise Dam gold deposit, Yilgarn Craton, Western Australia: a new occurrence of nagyágite - Y.-H. Sung; C. L. Ciobanu; A. Pring; J. Brügger; W. Skinner; N. J. Cook; M. Nugus (Mineralogy and Petrology, 2007)

Responses of Phradis parasitoids to volatiles of lavender, Lavendula angustifolia—a possible repellent for their host, Meligethes aeneus - Samantha M. Cook; Martin Jönsson; Matthew P. Skellern; Darren A. Murray; Peter Anderson; Wilf Powell (BioControl, 2007)

Isolation of viral haemorrhagic septicaemia virus from mummichog, stickleback, striped bass and brown trout in eastern Canada - N Gagné; A‐M MacKinnon; L Boston; B Souter; M Cook‐Versloot; S Griffiths; G Olivier (Journal of Fish Diseases, 2007)
Viral haemorrhagic septicaemia virus (VHSV) was isolated from mortalities occurring in populations of mummichog, Fundulus heteroclitus , stickleback, Gasterosteus aculeatus aculeatus , brown trout, Salmo trutta , and striped bass, Morone saxatilis , in New Brunswick and Nova Scotia, Canada. The isolated viral strains produced a cytopathic effect on the epithelioma papillosum cyprini cell line. Serum neutralization indicated the virus was VHSV and sequencing identified the rhabdovirus isolates as the North American strain of VHSV. Phylogenetic analysis indicated that the isolates are closely related and form a distinguishable subgroup of North American type VHSV. To our knowledge, this is the first report of VHSV in mummichog and striped bass.

Behavioural and chemical ecology underlying the success of turnip rape (Brassica rapa) trap crops in protecting oilseed rape (Brassica napus) from the pollen beetle (Meligethes aeneus) - S. M. Cook; H. B. Rasmussen; M. A. Birkett; D. A. Murray; B. J. Pye; N. P. Watts; I. H. Williams (Arthropod-Plant Interactions, 2007)

Thermal tolerance of a northern population of striped bass Morone saxatilis - A. M. Cook; J. Duston; R. G. Bradford (Journal of Fish Biology, 2006)
Thermal tolerance of age 0+ year Shubenacadie River (Nova Scotia, Canada) striped bass Morone saxatilis juveniles (mean ± s . e . fork length, L F , 19·2 ± 0·2 cm) acclimated in fresh water to six temperatures from 5 to 30° C was measured by both the incipient lethal technique (72 h assay), and the critical thermal method ( C m ). The lower incipient lethal temperature ranged from 2·4 to 11·3° C, and the upper incipient lethal temperature ( I U ) from 24·4 to 33·9° C. The area of thermal tolerance was 618° C 2 . In a separate experiment, the I U of large age 2+ year fish (34·4 ± 0·5 cm L F ) was 1·2 and 0·6° C lower ( P L F ) at acclimation temperatures of 16 and 23° C. Using the C m , loss of equilibrium occurred at 27·4–37·7° C, loss of righting response at 28·1–38·4° C and onset of spasms at 28·5–38·8° C, depending on acclimation temperature. The linear regression slopes for these three responses were statistically similar (0·41; P > 0·05), but the intercepts differed (25·3, 26·0 and 26·5° C; P

Populations of Myriophyllum alterniflorum L. as bioindicators of pollution in acidic to neutral rivers in the Limousin region - P. Chatenet; D. Froissard; J. Cook-Moreau; P. Hourdin; A. Ghestem; M Botineau; J. Haury (Hydrobiologia, 2006)

Enhanced sucrose pellet consumption induced by benzodiazepine-type drugs in squirrel monkeys: role of GABAA receptor subtypes - Angela N. Duke; Donna M. Platt; James M. Cook; Shengming Huang; Wenyuan Yin; Bruce A. Mattingly; James K. Rowlett (Psychopharmacology, 2006)

Evidence of an oscillating peripheral clock in an equine fibroblast cell line and adipose tissue but not in peripheral blood - Barbara A. Murphy; Mandi M. Vick; Dawn R. Sessions; R. Frank Cook; Barry P. Fitzgerald (Journal of Comparative Physiology A, 2006)

Biogeographic history of an Australian freshwater shrimp, Paratya australiensis (Atyidae): the role life history transition in phylogeographic diversification - B. D. COOK; A. M. BAKER; T. J. PAGE; S. C. GRANT; J. H. FAWCETT; D. A. HURWOOD; J. M. HUGHES (Molecular Ecology, 2006)
The widespread distribution of the freshwater shrimp Paratya australiensis in eastern Australia suggests that populations of this species have been connected in the past. Amphidromy is ancestral in these shrimps, although many extant populations are known to be restricted to freshwater habitats. In this study, we used a fragment of the cytochrome c oxidase I mitochondrial DNA (mtDNA) gene to examine diversity within P. australiensis and to assess the relative importance of amphidromy in its evolutionary history. We hypothesized that if transitions from an amphidromous to a freshwater life history were important, then we would find a number of divergent lineages restricted to single or groups of nearby drainages. Alternatively, if amphidromy was maintained within the species historically, we expected to find lineages distributed over many drainages. We assumed that the only way for divergence to occur within amphidromous lineages was if dispersal was limited to between nearby estuaries, which, during arid periods in the earth's history, became isolated from one another. We found nine highly divergent mtDNA lineages, estimated to have diverged from one another in the late Miocene/early Pliocene, when the climate was more arid than at present. Despite this, the geographic distribution of lineages and haplotypes within lineages did not support the notion of a stepping‐stone model of dispersal between estuaries. We conclude that the extensive divergence has most likely arisen through a number of independent amphidromy–freshwater life history transitions, rather than via historical isolation of amphidromy populations. We also found evidence for extensive movement between coastal and inland drainages, supporting the notion that secondary contact between lineages may have occurred as a result of drainage rearrangements. Finally, our data indicate that P. australiensis is likely a complex of cryptic species, some of which are widely distributed, and others geographically restricted.

Bactericidal effects of plasma-generated cluster ions - I. Digel; A. Temiz Artmann; K. Nishikawa; M. Cook; E. Kurulgan; G. M. Artmann (Medical & Biological Engineering & Computing, 2005)

Interaction between inflammation-related gene polymorphisms and cigarette smoking on the risk of myocardial infarction in the Physician’s Health Study - Sarah A. Rosner; Paul M. Ridker; Robert Y. L. Zee; Nancy R. Cook (Human Genetics, 2005)

Temporal resolution of the Florida manatee (Trichechus manatus latirostris) auditory system - David A. Mann; Debborah E. Colbert; Joseph C. Gaspard; Brandon M. Casper; Mandy L. H. Cook; Roger L. Reep; Gordon B. Bauer (Journal of Comparative Physiology A, 2005)

Variation in ITGB3 has sex-specific associations with plasma lipoprotein(a) and whole blood serotonin levels in a population-based sample - Lauren A. Weiss; Mark Abney; Rodney Parry; Angelo M. Scanu; Edwin H. Cook; Carole Ober (Human Genetics, 2005)

Postglacial expansion of the southern red‐backed vole ( Clethrionomys gapperi ) in North America - AMY M. RUNCK; JOSEPH A. COOK (Molecular Ecology, 2005)
Dynamic climatic oscillations of the Pleistocene dramatically changed the distributions of high latitude species. Molecular investigations of a variety of organisms show that processes of postglacial colonization of boreal regions were more complex than initially thought. Phylogeographical and coalescent analyses were conducted on partial sequences of the cytochrome b gene (600 bp) from 64 individuals of Clethrionomys gapperi from North Carolina, Pennsylvania, Minnesota, Idaho, Washington, British Columbia, Northwest Territories, and Alaska to test hypotheses relating to Pleistocene refugia and postglacial colonization routes. Three divergent clades (east, west, central) were identified with highest net divergence ( d A = 5.2%) between the eastern and western clades. Populations from the recently deglaciated higher latitudes of Canada and Alaska are closely related to lower latitude populations of the central clade ( d A = 1.2%) suggesting recent expansion from this midwestern region. No representatives from the east or west clade were found at latitudes higher than 50°N, indicating that postglacial colonization occurred through a midcontinental route. The high latitude population from the Northwest Territories exhibited demographic patterns and genetic diversity consistent with a stable noncolonizing population. This population is found near the Mackenzie range, where the two continental ice sheets were believed to have coalesced. Molecular variation observed in this population may be the result of leading edge population diversifying in the continental corridor or may reflect the signal of a high latitude refugial population.

Protocatechuate 4,5-dioxygenase from Comamonas testosteroni T-2: biochemical and molecular properties of a new subgroup within class III of extradiol dioxygenases - Jrg Mampel; Miguel A. Providenti; Alasdair M. Cook (Archives of Microbiology, 2005)

Field-Scale Experiments for Site-Specific Crop Management. Part II: A Geostatistical Analysis - M. J. Pringle; A. B. McBratney; S. E. Cook (Precision Agriculture, 2004)

Field-Scale Experiments for Site-Specific Crop Management. Part I: Design Considerations - M. J. Pringle; S. E. Cook; A. B. McBratney (Precision Agriculture, 2004)

GABAA/α1 receptor agonists and antagonists: effects on species-typical and heightened aggressive behavior after alcohol self-administration in mice - Rosa M. M. de Almeida; James K. Rowlett; James M. Cook; Wenyuan Yin; Klaus A. Miczek (Psychopharmacology, 2004)

Responses of the Aphids Phorodon humuli and Rhopalosiphum padi to Sex Pheromone Stereochemistry in the Field - Colin A. M. Campbell; Fraser J. Cook; John A. Pickett; Tom W. Pope; Lester J. Wadhams; Christine M. Woodcock (Journal of Chemical Ecology, 2003)

Influence of pasture management (nitrogen and lime addition and insecticide treatment) on soil organisms and pasture root system dynamics in the field - L. A. Dawson; S. J. Grayston; P. J. Murray; R. Cook; A. C. Gange; J. M. Ross; S. M. Pratt; E. I. Duff; A. Treonis (Plant and Soil, 2003)

Nitrous oxide emissions following application of residues and fertiliser under zero and conventional tillage - E.M. Baggs; M. Stevenson; M. Pihlatie; A. Regar; H. Cook; G. Cadisch (Plant and Soil, 2003)

Uptake of erythromycin by first‐feeding sockeye salmon, Oncorhynchus nerka (Walbaum), fed live or freeze‐dried enriched adult Artemia or medicated pellets - M A Cook; M B Rust; K Massee; T Majack; M E Peterson (Journal of Fish Diseases, 2003)
The potential to use adult Artemia to deliver erythromycin to first‐feeding sockeye salmon, Oncorhynchus nerka (Walbaum), was investigated in three trials. In the first trial, first‐feeding sockeye were fed live erythromycin enriched adult Artemia or pellets containing equal amounts of erythromycin for 35 days. At the end of the trial, tissue erythromycin concentration of the fish fed the live Artemia was significantly greater ( P μ g mL −1 ; mean ± SEM), than the tissue concentration of the fish fed the pellets (0.72 ± 0.01 μ g mL −1 ). In the second trial, first‐feeding sockeye were fed either live or freeze‐dried bioencapsulated erythromycin (adult Artemia ) or pellets containing erythromycin daily for 21 days. Mean daily erythromycin concentration in fish fed the freeze‐dried Artemia , live Artemia , or pellets did not differ significantly. In the third trial, apparent erythromycin digestibility was determined. Significantly more ( P Artemia (live or freeze‐dried) appears to be greater than uptake from pellets. Freeze‐dried and live Artemia were equally effective at delivery suggesting enriched freeze‐dried adult Artemia could be produced into a highly palatable, consistent, off‐the‐shelf product.

Holarctic phylogeography of the root vole ( Microtus oeconomus ): implications for late Quaternary biogeography of high latitudes - C. Brunhoff; K. E. Galbreath; V. B. Fedorov; J. A. Cook; M. Jaarola (Molecular Ecology, 2003)
A species‐wide phylogeographical study of the root vole ( Microtus oeconomus ) was performed using the whole 1140 base pair mitochondrial (mt) cytochrome b gene. We examined 83 specimens from 52 localities resulting in 65 unique haplotypes. Our results demonstrate that the root vole is divided into four main mtDNA phylogenetic lineages that seem to have largely allopatric distributions. Net divergence estimates (2.0–3.5%) between phylogroups, as well as relatively high nucleotide diversity estimates within phylogroups, indicate that the distinct phylogeographical structure was initiated by historical events that predated the latest glaciation. European root voles are divided into a Northern and a Central mtDNA phylogroup. The mtDNA data in concert with fossil records imply that root voles remained north of the classical refugial areas in southern Europe during the last glacial period. The currently fragmented populations in central Europe belong to a single mtDNA phylogroup. The Central Asian and the North European lineages are separated by the Ural Mountains, a phylogeographical split also found in collared lemmings ( Dicrostonyx ) and the common vole ( M. arvalis ). The Beringian lineage occurs from eastern Russia through Alaska to northwestern Canada. This distribution is congruent with the traditional boundaries of the Beringian refugium and with phylogeographical work on other organisms. In conclusion, similarities between the phylogeographical patterns in the root vole and other rodents, such as Arctic and subarctic lemmings, as well as more temperate vole species, indicate that late Quaternary geological and climatic events played a strong role in structuring northern biotic communities.

Deep Natural Gas Resources - T. S. Dyman; R. E. Wyman; V. A. Kuuskraa; M. D. Lewan; T. A. Cook (Natural Resources Research, 2003)

Phylogeography of lemmings ( Lemmus ): no evidence for postglacial colonization of Arctic from the Beringian refugium - V. B. Fedorov; A. V. Goropashnaya; M. Jaarola; J. A. Cook (Molecular Ecology, 2003)
Beringia is considered as an important glacial refugium that served as the main source for colonization of formerly glaciated Arctic regions. To obtain high resolution views of Arctic refugial history, we examined mitochondrial cytochrome b phylogeography in the northern genus of rodents, Lemmus ( true lemmings), sampled across its circumpolar distribution. Strong phylogeographical structure suggests vicariant separation over several glacial–interglacial periods and does not provide evidence supporting the importance of Beringia for extensive colonization of formerly glaciated regions. Rather than a source of postglacial colonization, Beringia represents an area of intraspecific endemism previously undetected by biogeographical analysis. Existing phylogeographical structure suggests that vicariant separation by glacial barriers was an important factor generating genetic divergence and, thus, increasing genetic diversity in lemmings on continental and circumpolar scales. However, there is little evidence for the direct effect of the last glaciation on the level of genetic variation and allele genealogy in lemmings on a regional geographical scale. This finding implies that the population genetic models of postglacial colonization suggested for temperate taxa might have limited applicability for Arctic species.

Bioencapsulation of five forms of erythromycin by adult Artemia salina (L.) - M A Cook; M B Rust (Journal of Fish Diseases, 2002)
Uptake of five chemical forms of erythromycin by adult Artemia salina (L.) (erythromycin phosphate – EP, erythromycin stearate – ES, erythromycin estolate – EE, erythromycin hydrate – EH and crystalline erythromycin – CE) was investigated in two trials. In each trial, final erythromycin concentration in Artemia tissue and survival after a 12‐h bioencapsulation period were determined. In the first trial, Artemia tissue concentration after a 12‐h bioencapsulation period was significantly ( P −1 , mean ± SEM) ≈ EH (61.2 ± 3.4 μg mL −1 ) > CE (37.1 ± 10.7 μg mL −1 ) > EP (16.4 ± 7.7 μg mL −1 ) > control. In trial 2, Artemia tissue concentration was also significantly ( P −1 ) > CE (89.1 ± 1.7 μg mL −1 ) > ES (78.9 ± 1.6 μg mL −1 ) > EP (33.4 ± 5.2 μg mL −1 ) > control. Survival was significantly affected by erythromycin form in trial 1 with EP=control (100 ± 0.0%) > ES (74.4 ± 2.0%) > CE (32.2 ± 0.3%) > EH (8.8 ± 4.4%). In trial 2, survival was also significantly affected by erythromycin form with EP=control (100 ± 0.0%) > ES (67.1 ±3.7%) > CE (52.5 ± 7.7%) > EE (5.0 ± 2.5%). Based on both uptake and survival, EP and ES appear to be appropriate compounds for bioencapsulation of erythromycin using live adult Artemia .

Molecular analysis of the genotype-phenotype relationship in factor VII deficiency - D. Millar; G. Kemball-Cook; J. McVey; E. Tuddenham; A. Mumford; G. Attock; J. Reverter; N. Lanir; L. Parapia; J. Reynaud; E. Meili; A. von Felton; et al. (Human Genetics, 2000)

Phytosociological analysis of restored and managed grassland habitat within an urban national park - Andrew M. Greller; Celestine Durando; Leslie F. Marcus; D. Siril A. Wijesundara; Michael D. Byer; Robert Cook; John T. Tanacredi (Urban Ecosystems, 2000)

Hepatitis E virus infection in chimpanzees: a retrospective analysis - K. A. McCaustland; K. Krawczynski; J. W. Ebert; M. S. Balayan; A. G. Andjaparidze; J. E. Spelbring; E. H. Cook; C. Humphrey; P. O. Yarbough; M. O. Favorov; D. Carson; D. W. Bradley; et al. (Archives of Virology, 2000)

Seasonal soil‐surface carbon fluxes from the root systems of young Pinus radiata trees growing at ambient and elevated CO 2 concentration - Stephen M. Thomas; Freeman J. Cook; David Whitehead; John A. Adams (Global Change Biology, 2000)
Summary Elevated atmospheric CO 2 concentration may result in increased below‐ground carbon allocation by trees, thereby altering soil carbon cycling. Seasonal estimates of soil surface carbon flux were made to determine whether carbon losses from Pinus radiata trees growing at elevated CO 2 concentration were higher than those at ambient CO 2 concentration, and whether this was related to increased fine root growth. Monthly soil surface carbon flux density ( f ) measurements were made on plots with trees growing at ambient (350) and elevated (650 μmol mol −1 ) CO 2 concentration in large open‐top chambers. Prior to planting the soil carbon concentration (0.1%) and f (0.28 μmol m −2 s −1 at 15 °C) were low. A function describing the radial pattern of f with distance from tree stems was used to estimate the annual carbon flux from tree plots. Seasonal estimates of fine root production were made from minirhizotrons and the radial distribution of roots compared with radial measurements of f . A one‐dimensional gas diffusion model was used to estimate f from soil CO 2 concentrations at four depths. For the second year of growth, the annual carbon flux from the plots was 1671 g y −1 and 1895 g y −1 at ambient and elevated CO 2 concentrations, respectively, although this was not a significant difference. Higher f at elevated CO 2 concentration was largely explained by increased fine root biomass. Fine root biomass and stem production were both positively related to f. Both root length density and f declined exponentially with distance from the stem, and had similar length scales. Diurnal changes in f were largely explained by changes in soil temperature at a depth of 0.05 m. Ignoring the change of f with increasing distance from tree stems when scaling to a unit ground area basis from measurements with individual trees could result in under‐ or overestimates of soil‐surface carbon fluxes, especially in young stands when fine roots are unevenly distributed.

The activity of the H + -monocarboxylate cotransporter during pre-implantation development in the mouse - E. A. Harding; M. L. Day; C. A. Gibb; M. H. Johnson; D. I. Cook (Pflügers Archiv - European Journal of Physiology, 1999)

Use of replication-deficient adenoviruses to study signal transduction pathways. Muscarinic responses in HSG and HT29 epithelial cell lines are mediated by G protein βγ-subunits - P. Poronnik; L. M. O'Mullane; A. D. Conigrave; D. I. Cook (Pflügers Archiv - European Journal of Physiology, 1999)

Nitric oxide donors, sodium nitroprusside and S-nitroso-N-acetylpenicillamine, stimulate myoblast proliferation in vitro - J. A. Ulibarri; P. E. Mozdziak; E. Schultz; C. Cook; T. M. Best (In Vitro Cellular & Developmental Biology - Animal, 1999)

The incidence of gastric carcinoma in Asian migrants to the United States and their descendants - Aruna Kamineni; Michelle A. Williams; Stephen M. Schwartz; Linda S. Cook; Noel S. Weiss (Cancer Causes & Control, 1999)

Growth, loss, and vertical distribution of Pinus radiata fine roots growing at ambient and elevated CO 2 concentration - Stephen M. Thomas; David Whitehead; JefF. B. Reid; Freeman J. Cook; JohN. A. Adams; AlaN. C. Leckie (Global Change Biology, 1999)
Increased below‐ground carbon allocation in forest ecosystems is a likely consequence of rising atmospheric CO 2 concentration. If this results in changes to fine root growth, turnover and distribution long‐term soil carbon cycling and storage could be altered. Bi‐weekly measurements were made to determine the dynamics and distribution of fine roots ( Pinus radiata trees growing at ambient (350 μmol mol –1 ) and elevated (650 μmol mol –1 ) CO 2 concentration in large open‐top chambers. Measurements were made using minirhizotrons installed horizontally at depths of 0.1, 0.3, 0.5 and 0.9 m. During the first year, at a depth of 0.3 m, the increase in relative growth rate of roots occurred 6 weeks earlier in the elevated CO 2 treatment and the maximum rate was reached 10 weeks earlier than for trees in the ambient treatment. After 2 years, cumulative fine root growth ( P t ) was 36% greater for trees growing at elevated CO 2 than at ambient CO 2 concentration, although this difference was not significant. A model of root growth driven by daily soil temperature accounted for between 43 and 99% of root growth variability. Total root loss ( L t ) was 9% in the ambient and 14% in the elevated CO 2 treatment, although this difference was not significant. Root loss was greatest at 0.3 m. In the first year, 62% of fine roots grown between mid‐summer and late‐autumn disappeared within a year in the elevated CO 2 treatment, but only 18% in the ambient CO 2 treatment ( P L t to time accounted for between 74 and 99% of the variability. Root cohort half‐lives were 951 d for the ambient and 333 d for the elevated treatment. Root length density decreased exponentially with depth in both treatments, but relatively more fine roots grown in the elevated CO 2 treatment tended to occur deeper in the soil profile.

Wolbachia in two insect host–parasitoid communities - S. A. WEST; J. M. COOK; J. H. WERREN; H. C. J. GODFRAY (Molecular Ecology, 1998)
Wolbachia form a group of intracellular bacteria that alter reproduction in their arthropod hosts. Two major phylogenetic subdivisions (A and B) of Wolbachia occur. Using a polymerase chain reaction assay we surveyed for the A and B group Wolbachia in 82 insect species from two temperate host–parasitoid communities (food webs) and a general collection of Lepidoptera caught at a light trap. One host–parasitoid community was based around leaf‐mining Lepidoptera, and the other around Aphids. We found that: (i) 22.0% of insects sampled were infected with Wolbachia ; and (ii) the prevalence and type (A or B) of Wolbachia infection differed significantly between communities and taxonomic groups. We obtained DNA sequences from the ftsZ gene for the group B Wolbachia found in six leaf‐mining species and one of their parasitoids, as well as four of the Lepidoptera caught by a light trap. Taken together, the results of our survey and phylogenetic analyses of the sequence data suggest that host–parasitoid transfer of Wolbachia is not the major route through which the species we have examined become infected. In addition, the Wolbachia strains observed in five leaf‐mining species from the same genus were not closely related, indicating that transfer between species has not occurred due to a shared feeding niche or cospeciation.

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

Comparison of Ceralure and Trimedlure Controlled-Release Formulations for Male Mediterranean Fruit Flies in C&C Traps - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1998)

The effect of severe eccentric exercise-induced muscle damage on plasma elastase, glutamine and zinc concentrations - M. Gleeson; N. P. Walsh; A. K. Blannin; P. J. Robson; L. Cook; A. E. Donnelly; S. H. Day (European Journal of Applied Physiology, 1998)

Cytokinesis and nodal anatomy in the charophycean green alga Chara zeylanica - M. E. Cook; L. E. Graham; C. A. Lavin (Protoplasma, 1998)

The effects of high-intensity intermittent exercise on the plasma concentrations of glutamine and organic acids - N. P. Walsh; A. K. Blannin; A. M. Clark; L. Cook; P. J. Robson; M. Gleeson (European Journal of Applied Physiology, 1998)

Homology modelling of the catalytic domain of early mammalian protein C: evolution of structural features - A. I. Wacey; M. Krawczak; G. Kemball-Cook; D. N. Cooper (Human Genetics, 1997)

Thiosulfate as a metabolic product: the bacterial fermentation of taurine - Karin Denger; Heike Laue; A. M. Cook (Archives of Microbiology, 1997)

Fermentation of cysteate by a sulfate-reducing bacterium - Heike Laue; Karin Denger; A. M. Cook (Archives of Microbiology, 1997)

Improved Controlled-Release Formulations for a New Trap Design for Male Mediterranean Fruit Flies: The C&C Trap - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1997)

Assimilation of sulfur from alkyl- and arylsulfonates by Clostridium spp. - Karin Denger; A. M. Cook (Archives of Microbiology, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Purification of ribulose 1,5-bisphosphate carboxylase/oxygenase and of carboxysomes from Thiobacillus thyasiris the putative symbiont of Thyasira flexuosa (Montagu) - Tom Lanaras; Catherine M. Cook; Ann P. Wood; Don P. Kelly; Geoffrey A. Codd (Archives of Microbiology, 1991)

Effect of in ovo bursectomy on the course of an infectious bronchitis virus infection in line C White Leghorn chickens - J. K. A. Cook; T. F. Davison; M. B. Huggins; P. McLaughlan (Archives of Virology, 1991)

A recombinant fowlpox virus that expresses the VP2 antigen of infectious bursal disease virus induces protection against mortality caused by the virus - C. D. Bayliss; R. W. Peters; Jane K. A. Cook; R. L. Reece; K. Howes; M. M. Binns; M. E. G. Boursnell (Archives of Virology, 1991)

Dichloromethane utilized by an anaerobic mixed culture: acetogenesis and methanogenesis - Susanna A. Stromeyer; Wolfgang Winkelbauer; Herbert Kohler; Alasdair M. Cook; Thomas Leisinger (Biodegradation, 1991)

Difference in metabolic profile of potassium canrenoate and spironolactone in the rat: Mutagenic metabolites unique to potassium canrenoate - Chyung S. Cook; Charles L. Hauswald; Grant L. Schoenhard; Charles E. Piper; Arun Patel; Frederick M. Radzialowski; Jeremy D. Hribar; William Aksamit; Pat Finnegan; Roy H. Bible; James A. Oppermann (Archives of Toxicology, 1988)

The influence of the bone-implant interface stiffness on stress profiles surrounding Al2O3 and carbon dental implants - C. J. Lavernia; S. D. Cook; A. M. Weinstein; J. J. Klawitter (Annals of Biomedical Engineering, 1982)

Evidence for the in vivo regulation of glucose 6-phosphate dehydrogenase activity in Hydrogenomonas eutropha H 16 from measurements of the intracellular concentrations of metabolic intermediates - B. Bowien; A. M. Cook; H. G. Schlegel (Archives of Microbiology, 1974)

Sectional notes - Frank E. Garrett; Roy M. Barnes; W. Frank McGee; A. H. Eddins; W. B. Ward; Verne C. Beverly; H. A. Reiley; Allan W. Purdy; J. C. Campbell; H. J. Evans; Harold Mattson; O. D. Burke; et al. (American Journal of Potato Research, 1947)

The effect of different amounts of spindle tuber and leaf roll on yields of Irish potato - E. L. Leclerg; P. M. Lombard; A. H. Eddins; H. T. Cook; J. C. Campbell (American Journal of Potato Research, 1944)

Effect of different amounts of spindle tuber and leaf roll on yields of Irish potatoes - E. L. Leclerg; P. M. Lombard; A. H. Eddins; H. T. Cook; J. C. Campbell (American Journal of Potato Research, 1944)